Guardians of privacy in the age of artificial intelligence: Librarians’ roles and realities in the Fourth Industrial Revolution: A case study involving two academic libraries in Cape Town - Ocks, Yumnaa; Salubi, Oghenere G. (South African Journal of Information Management, 2026)
Background: The Fourth Industrial Revolution (4IR) has introduced transformative technologies into academic libraries, offering opportunities to enhance access, efficiency and service delivery. The increasing reliance on digital platforms, data-driven tools and third-party services raises challenges regarding privacy, data protection and ethical information management. Objectives: This study was guided by two research objectives. Firstly, it sought to investigate the current and projected adoption of 4IR technologies in academic libraries to enhance service provision. Secondly, it aimed to examine academic librarians’ concerns regarding user privacy within these evolving technological practices. Method: Drawing on a case study of two academic libraries in Cape Town, this study examines librarians’ awareness, perceptions, and practices concerning data privacy, cybersecurity and regulatory compliance with the Protection of Personal Information Act. Using a qualitative case study of two anonymised academic libraries in Cape Town, the study examined librarians’ awareness, perceptions and practices regarding data privacy, cybersecurity and compliance with the POPI Act. The study also used thematic analysis to interpret the data and to provide insight into how institutional policies and technological infrastructures shape librarians’ responses to data protection obligations. Furthermore, the study highlights emerging challenges and opportunities for strengthening privacy practices within academic libraries in the context of evolving digital environments. Results: Findings reveal that while libraries acknowledge the importance of privacy and confidentiality, gaps remain in institutional policies, technical capacity and staff training. The findings suggest that libraries must adopt a multidimensional approach, strengthening cybersecurity, enhancing ethical governance, fostering collaboration and investing in continuous staff development. Conclusion: The study argues for a multidimensional approach that combines robust cybersecurity measures, ethical governance, collaboration and continuous staff development to safeguard patron confidentiality while advancing innovation. Contribution: Libraries must navigate the intersection of technological advancement and ethical responsibility, while ensuring that emerging technologies reinforce, rather than undermine the values of access, equity and privacy.

Investigating the usability, feasibility, and effect of a virtual reality cognitive training system on brain cancer patients with mild cognitive impairment: a quasi-experimental (single-arm) pilot study - Faiola, Anthony; Soroya, Saira (medRxiv, 2026)
Abstract (1) Background Brain cancer is the ninth leading cause of cancer death in the US, with approximately 76,000 newly diagnosed cases annually. Studies show that at time of diagnosis, up to six-months post-treatment, 50%–80% of brain cancer survivors (BCS) report cognitive dysfunction. Mild cognitive impairment (MCI) has gained increasing attention as a persistent disability experienced by up to 75% of all BCS, which affects memory, concentration, executive function, etc. Studies show cognitive training with computerized gaming as improving cognitive function for patients with stroke, dementia, and Parkinson’s. It is of significant clinical interest to develop innovative interventions that reduce MCI. Aim: To improve cognitive performance of BCS suffering with MCI by evaluating the feasibility, acceptability and effect of a Virtual Reality Cognitive Rehabilitation Training (VR-CRT) platform during four weeks of cognitive training (2) Methods We employed a quasi-experimental pretest/posttest non-randomized/non-blinded single-arm design for 4 weeks, with an experimental group (n=6, after attrition) using VR-CRT. Participants were selected based on convenience sampling using the electronic medical record to identify qualified patients, guided by inclusion/exclusion criteria. Feasibility was defined by retention as >80%, with usability testing using the System Usability Scale (SUS) and NASA-TLX surveys. The Hopkins Verbal Learning Test (HVLT), Controlled Oral Word Association (COWA) test, and Trail Making A-B (TM-A/B) test were used to measure cognitive performance, comparing baseline to post week-four. (3) Results The feasibility criteria of >80% was met. All SUS and NASA scores were in the higher index, suggesting a high degree of usability, with low workload demand. For effect, the COWA findings showed a significant improvement (41.38%), with a paired sample T-Test confirming that the participants’ COWA scores improved significantly from pre- to post-intervention ( p = 0.03), indicating enhanced verbal fluency and executive functioning after intervention. HVLT (combined) showed improvements of 18.75% for Form A and 11.32% for Form B, which also showed a significant improvement ( p = .04) in the retention discrimination index from pre- to post-test. The TM-A/B test showed an improvement (25.97%), suggesting that the participants spent less time completing both parts A and B, but was not statistically significant. (4) Conclusion This study fulfilled our aim to demonstrate modest to significant cognitive improvement using VR-CRT with brain cancer patients with MCI. Despite the small sample size, we believe the use of virtual reality will lead to important advances for patients with MCI, particularly the frontal lobe brain region, expressed in executive function.
Keywords: Cognition; Cognitive rehabilitation therapy; Cognitive training; Psychological intervention; Rehabilitation; Test (biology); Usability; Virtual reality; Workload; dept.ils

The influence of responsible leadership on organizational commitment: the mediating role of trust in leaders in the higher education sector - Afzal, Muhammad; Soroya, Saira; Chaudhary, Naveed; Niazi, Abdul; Ashiq, Murtaza (RADS Journal of Business Management, 2025)
Background: This study examines the impact of responsible leadership (RL) on organizational commitment by examining the mediating role of trust in the leader, as modeled by the four key dimensions of the leader's role (aggregate of virtues, principles and ethical values, stakeholder involvement, and model of the leader's role) in the context of social identity theory. Methods: We employed a quantitative research design, surveying 300 middle-level employees in grades 11 to 16 from the University of the Punjab, Lahore, Pakistan. Data collection involved a structured questionnaire covering key leadership and trust dimensions. The data analysis utilized SPSS version 22 and ADANCO version 2.2, with structural equation modeling to test hypotheses. Results: Results show that organizational commitment is significantly influenced by stakeholder involvement (0.03 p-value) and ethical principles (0.00 p-value). The aggregate of virtues (0.79 p-value) and leadership role modeling (0.26 p-value) have an insignificant direct impact. However, trust significantly mediates the relationship between organizational commitment and stakeholder involvement (0.01 p-value). Trust’s mediation effect on the link between ethical principles and organizational commitment is minimal (0.04 p-value). Conclusion: This study suggests that implementing RL practices, particularly in stakeholder involvement and ethical leadership, enhances employee commitment. Responsible leadership cultivates a positive corporate image, attracting committed stakeholders. To maximize benefits, organizations should provide senior leaders with behavioral training in RL practices, fostering an environment that boosts employee loyalty. Leadership development programs should include modules on ethical decision-making, stakeholder communication, and trust-building strategies.
Keywords: Context (archaeology); Ethical leadership; Mediation; Organizational commitment; Stakeholder; Stakeholder engagement; Stakeholder theory; Structural equation modeling; dept.ils

Mental Health Needs of Families of Patients in Intensive Care Units and the Role of Mobile Health: Survey Study - Faiola, Anthony; Soroya, Saira; Hao, Zhonglin; Munker, Reinhold (JMIR Formative Research, 2025)
BACKGROUND: The experiences of patients with COVID-19 and their families manifested the most devastating effects of family separation since the 1918 Spanish influenza pandemic and, with it, a call for solutions to patient isolation and its effect on family mental health. OBJECTIVE: This study examined the recent experiences of families of critical care (intensive care unit; ICU) patients related to anxiety and depression (AD), satisfaction with clinician-family communication, and counseling from mental health and social services. This study explored correlations between these factors and family interest in mobile health (mHealth) designed to improve information flow and communication from patient bedside to remote families. METHODS: Using a 36-question quantitative survey, we collected 97 responses over 6 months. We selected participants by using a convenience sampling strategy. To analyze data, we applied descriptive and inferential statistics. Participants represented a spectrum of ages, relationships to patients, and races (n=78, 80% White; n=17, 18% Black; n=2, 2% other races). Approximately 17% (n=16) of the patients were admitted for cancer, 13% (n=13) were admitted for COVID-19, and 21% (n=20) were admitted for other conditions. RESULTS: The mean score for remote families' satisfaction with patient health updates from the bedside and mental health services was 2.94 (SD 1.31), whereas that for phone communication was lower on average. The mean scores of family AD levels were elevated, and levels were higher among family members during the ICU stay than after discharge. These findings confirmed evidence of a negative correlation between transportation difficulties and satisfaction with the frequency of information provided (r=-0.284; P=.005), suggesting that, with the increase in transportation challenges, families become less satisfied with the frequency of patient health information. Family members expressed strong interest in using mHealth information and communication services (mean 8.34, SD 1.98) and having easy access to social workers to manage AD (mean 8.29, SD 2.03). Families experiencing higher levels of anxiety during patients' ICU stays had significantly greater interest in the use of an mHealth app that would provide direct access to social workers (r=0.326; P<.001), in using an mHealth videoconferencing app (r=0.319; P=.002), and in overall mHealth app use (r=0.322; P<.001). CONCLUSIONS: Family members experienced high levels of AD during patient ICU admission, as well as after discharge even though their mental health challenges were reduced. Families were highly dissatisfied with the frequency of health updates, with lower satisfaction reported among those who faced difficulties arranging transportation or lived further from the hospital. Modest but statistically significant correlations were observed between family members' reported mental health status during ICU stays and an interest in an mHealth app that could provide access to real-time bedside information, facilitate communication with bedside nurses, and support connections with social workers.
Keywords: Affect (linguistics); COVID-19; Depression (economics); Health care; ICU; Mental health; Mental illness; Receipt; communication; dept.ils; digital tools; eHealth; health equity; health technology; intensive care unit; mental health; mobile health

Investigating the Feasibility, Usability, and Efficacy of a Mobile App to Reduce Anxiety and Depression in Families of Critical Care Cancer Patients: A Quasi-Experimental Pilot Study - Faiola, Anthony; Soroya, Saira; Munker, Reinhold; Hao, Zhonglin; Lambert, Joshua (Healthcare, 2026)
Background: Cancer patients admitted to the bone marrow transplant (BMT) unit face life-threatening medical conditions. Consequently, their family members experience uncertainty, resulting in high levels of anxiety and depression (AD). Limited updates and communication from medical staff exacerbate these emotional burdens. To address these challenges, we developed a mobile health (mHealth) intervention, FamCarePlus, and evaluated its feasibility, usability, and efficacy. We hypothesized that the FamCarePlus application would demonstrate a high degree of feasibility and usability and would reduce AD compared to a control group relying solely on traditional communication through the nurses’ station. Methods: We employed a quasi-experimental pretest/posttest non-randomized, non-blinded self-report design over 3 weeks, with an experimental group (n = 10) using FamCarePlus and a control group (n = 9). We selected participants via convenience sampling using the electronic medical record to identify eligible patients and families, guided by inclusion and exclusion criteria. We used descriptive statistics and the Hospital Anxiety and Depression Scale (HADS) guidelines to analyze the data. Feasibility was defined by a retention rate > 80%, with usability testing using the System Usability Scale (SUS) and NASA Task Load Index (NASA-TLX) surveys. The HADS measured AD, comparing baseline to Week 3. Results: We met our feasibility criteria of >80%. All SUS and NASA scores were in the higher index, suggesting a significant degree of usability and low workload demand on participants. For efficacy, we compared baseline mean scores, with the experimental group reporting lower AD levels at Week 1 (41.9% and 27.8%, respectively) than the control group (55.2% and 34.2%, respectively). From Week 1 to Week 3, the percentage change showed an 8.6% decrease in anxiety in the experimental group, compared to a 12.8% decrease in anxiety in the control group. These results were consistent when analyzed according to HADS guidelines. Conclusions: The findings of this study provide preliminary evidence that the FamCarePlus intervention is feasible and usable, while also demonstrating that its use may be associated with a sustained reduction in AD levels among family members of patients admitted to the BMT unit. These outcomes underscore the potential of digital interventions to address disparities in patient health information access and psychosocial support.
Keywords: Anxiety; Depression (economics); Descriptive statistics; Hospital Anxiety and Depression Scale; System usability scale; Usability; Workload; anxiety; cancer; depression; dept.ils; families; intensive care unit; mHealth

Advancing Library Services for Mobile Users - Liu, Yan Quan (IGI Global Scientific Publishing, 2025)
As mobile technology becomes integral to everyday life, libraries rework their services to meet the needs of their users. Advancing library services for mobile users requires seamless, intuitive experiences that support research, learning, and engagement. From mobile-friendly catalogs and e-book pla...
Publication Title: https://services.igi-global.com/resolvedoi/resolve.aspx?doi=10.4018/978-1-7998-9175-8
Keywords: dept.ils

A Study of the Coverage of Open Educational Resources (OER) Through Websites of Colleges and Universities in Connecticut - Brown, Mary; Kim, Hak Joon (Practical Academic Librarianship: The International Journal of the SLA Academic Division, 2025)
Notwithstanding reports of increased awareness and use of Open Educational Resources (OER) in higher education, the literature notes that awareness and use of and institutional support for OER remain major challenges to campuses seeking to reduce student cost burden and support access to materials. OER also support faculty who desire to move beyond the traditional textbooks in order to increase their students’ engagement and thereby access to learning, to support pedagogical changes they are making that enhance student learning, and to give faculty greater control over their courses. The university website, as a public-facing vehicle to aid students, parents, alumni, faculty, the community, and interested others in being aware, among other things, of the resources available, is examined for findable support for OER. The purpose of this study is to show, through examination of their websites, a snapshot of the response of Connecticut universities and colleges to OER. Through an examination of these websites, we gage the ability to connect with information related to OER through the university website.
Keywords: dept.ils

Artificial Intelligence, Misinformation, and Libraries: A New Frontier for Information Professionals - Salubi, Oghenere (Proceedings of the Association for Information Science and Technology, 2025)
Generative artificial intelligence (AI) has experienced rapid advancement, fundamentally transforming the information landscape. This technological shift has not only amplified the dissemination of misinformation but has also posed significant challenges to conventional frameworks of trust and verification. This paper explores the dual impact of AI: its potential to enhance information services while simultaneously amplifying misinformation and disinformation. Seven AI-generated misinformation cases between 2022 and 2025—ranging from deepfakes and political propaganda to impersonation and amplification were analyzed. Through thematic case analysis and interdisciplinary synthesis, the study proposes the AI-Misinformation Resilience Model (AIM-RM), a conceptual framework guiding proactive responses across verification infrastructure, digital literacy, and ethical policy engagement. Drawing on recent scholarly literature and grounded in information ethics, epistemic trust, and sociocultural literacy, the model offers a path forward for LIS professionals seeking to navigate the post-truth era. Annual Meeting of the Association for Information Science & Technology | Nov. 14 – 18, 2025 | Washington, DC, USA.
Keywords: Deepfakes; Generative artificial intelligence; Information literacy; Library and information professionals; Misinformation; dept.ils

Developing a Video Game Metadata Schema and Fillable Form Template for Accessible Interactive Media Cataloging in Public Libraries - Myers, Jason (Cataloging & Classification Quarterly, 2025)
Keywords: Cataloging; Computer science; Information retrieval; Metadata; Multimedia; Schema (genetic algorithms); Video game; World Wide Web; cataloging interactive media; dept.ils; fillable forms; metadata schema; public libraries; video games

Inclusive Access: Evaluating Public Library Resources for Visually and Hearing Impaired Communities - Liu, Yan Quan; Buedinger, Abigale; Murtha, Helene R. (Public Library Quarterly)
This study examines public library services for people with hearing and vision impairments, conducted through website visits and an online survey from summer 2023 over 1.5 years. Surveying 250 libraries nationwide, findings reveal strong ADA awareness, with most libraries addressing physical accessibility but fewer supporting visually impaired and Deaf or Hard of Hearing patrons equally. Assistive resources availability varies significantly, from 0.8% to 83.4%, covering accessible print materials, online resources, magnifiers, and assistive technology. This study underscores specific areas for improvement in supporting these communities in U.S. public libraries.
_eprint: https://doi.org/10.1080/01616846.2025.2532895
Keywords: Accessibility; American with Disabilities Act (ADC); SCSU-student; dept.ils; hearing impairments; library services; vision impairments

Adopting Critical Cataloging Practices Post Diversity Audit: Connecting the Community to Your Collection - Anderson, Jessica K.; Liu, Yan Quan (Library Resources & Technical Services, 2025)
To increase patrons’ ability to find resources, it is imperative to investigate barriers and biases in thedescriptive catalog data for inclusive collection management and development standards. This studyused a specially designed descriptive approach to gather quantitative data from 101 public librariansin Connecticut via a Qualtrics survey to identify the key variables that influence the successfulenhancement of online public access catalog (OPAC) metadata after a diversity audit of the librarymaterials. The results revealed factors that promote or impede the integration of inclusive catalogingthat reflects the diversity of the community: (1) appreciating the benefits of audit methods that arefocused on bibliographic records, (2) recognizing the need for buy-in and participation from theentire organization, and (3) stressing the useful integration of institutional and community feedbackto improve the collection’s accessibility and representation. The findings provide practical adviceto public libraries that want to satisfy the diverse demands of their user base by integrating criticalcataloging frameworks into their diversity and inclusion objectives.
Keywords: SCSU-student; dept.ils

Digitization Practices in U.S. Urban Libraries: Tools, Technologies, and Metadata Standards - Torres, Natalia; Liu, Yan (Public Library Quarterly, 2025)
Keywords: Business; Computer science; Cultural heritage preservation; Data science; Digitization; Engineering; Library science; Metadata; SCSU-student; Telecommunications; World Wide Web; dept.ils; digital collections; digitization practices; online accessibility; urban libraries

Integrating tacit knowledge transfer model in academic context: a sem analysis approach - Shahzad, I.; Soroya, S.H. (Journal of the Knowledge Economy, 2025)
Tacit knowledge is more precious as compared to explicit, as it is the intellectual property of the knower and resides in one’s mind. A major part of our knowledge is tacit, which is either lost or not recorded/ captured. In the late 1950s, the term “tacit knowledge” appeared in the literature and received the attention of the researchers. However, a majority of the studies pertaining to tacit knowledge (TK) have primarily focused on non-educational contexts, despite the fact that pragmatic knowledge holds paramount importance within academic settings. This study is designed to examine the tacit knowledge process from capturing to sharing in an academic setting. A cross-sectional questionnaire-based survey research method was adopted to conduct this research, and data was collected through a well-structured questionnaire. Postgraduate students at the University of the Punjab, Lahore, Pakistan, were the study population. The findings revealed that cognitive skills enable and motivate individuals to capture tacit knowledge, and the positive capturing behavior leads to better handling and more sharing of tacit knowledge, whereas technical skills enable them to better handle tacit knowledge, which ultimately leads to wise utilization of tacit knowledge, and social skills help them in capturing, keeping, and use of tacit knowledge. The study argues that tacit knowledge flow is depending on a certain set of skills and behavior. The findings of the study will be supportive of higher academic institutions as they are the powerhouse of knowledge creation. © This is a U.S. Government work and not under copyright protection in the US; foreign copyright protection may apply 2024.
Keywords: Higher education; Implicit knowledge; Knowledge management; Social behaviors; dept.ils; peer-reviewed

Perceived awareness, benefits, and strategies of Pakistani editors regarding open-access journal publishing - Raza, Muhammad Zahid; Rafiq, Muhammad; Soroya, Saira Hanif (Global Knowledge, Memory and Communication, 2025)
This study aims to discover the perceived awareness, benefits and suitable strategies of the Pakistani editors of Higher Education Commission (HEC)-recognized scholarly journals regarding open-access (OA) journal publishing in Pakistan.,A structured questionnaire-based survey method of quantitative research approach was adopted to achieve the study’s objectives by collecting data from the editors of 329 HEC-recognized journals in Pakistan.,The awareness level of the respondents of the Pakistani journals is low regarding the OA concepts, resources and initiatives. The respondents of OA journals have better awareness levels than the respondents of non-OA journals. All the respondents of journals are convinced and have the view that OA journals have wider benefits for the academic community, and they need to flourish. A majority of the respondents are of the view that HEC should sponsor financial resources and technical training for OA journal publishing. The respondents of OA journals are more in favor of supporting OA journal publishing than the respondents of non-OA journals.,This study covered the lists of HEC-recognized journals of 2019. More studies may be conducted based on updated lists of HEC-recognized journals by using different research paradigms such as qualitative or pragmatic research approaches.,To the best of the authors’ knowledge, this study is the first comprehensive study on this phenomenon and is an effort to fill this gap and invigorate the scholarly literature. It may attract the attention of the policymakers, funding bodies, parent institutions of the journals and the HEC to cope with the low awareness level of the Pakistani editors regarding the OA concepts, resources and initiatives; and suitable strategies required to uplift the OA journal publishing paradigm in Pakistan.
Keywords: dept.ils; peer-reviewed

Perceptions of the Pakistani editors for open access journal publishing: a developing country’s perspective - Raza, Muhammad; Rafiq, Muhammad; Soroya, Saira (Information Development, 2025)
Objectives This study has been designed to determine Pakistani editors’ perceptions regarding the Open Access (OA) publishing practices of the Higher Education Commission (HEC)-recognized journals in Pakistan, and to assess their best OA publishing models. Methodology A structured questionnaire-based survey method of quantitative research approach was adopted to achieve the study’s objectives by collecting data from the editors of all 329 HEC-recognized journals in Pakistan. Findings This study exposed that public and teaching institutes are leading in OA journal publishing in Pakistan as compared to private and research institutes. Diamond OA, and Gold OA publishing models are popular among the respondents; however, respondents are not convinced to follow any specific OA publishing model due to their different choices. A large majority (92%) of the journals belong to the Y category (the lowest) of journals. A large majority (72%) of the journals in Pakistan is adopting the Open Journal System (OJS), and parent institutions installed web browsers. CC-BY-NC and CC-BY licenses are their favorite licenses. Significance The present study is the first comprehensive study on editors’ perceptions for OA journal publishing and is an effort to fill this gap to invigorate the scholarly literature. This study may enable the journals, editors, and publishers to follow the best OA journal publishing practices of the Pakistani journals for global OA usage of scholarly journals. The results have practical and theoretical ramifications for academic and research institutions, federal and provincial higher education commissioners, policy organizations, and parent institutions of journals.
Keywords: Computer science; Developing country; Economic growth; Economics; Library science; MEDLINE; Media studies; Open access journal; Open access publishing; Perception; Perspective (graphical); Political science; Psychology; Public relations; Publishing; Scopus; Sociology; dept.ils; peer-reviewed

Emerging Trends of Acquisition in Public Libraries of Pakistan: Challenges and Issues - Bashir, Faiza; Hanif Soroya, Saira; Soroya, M. Shahid; Khanum, Almas (Library Collections, Acquisitions, & Technical Services, 2015)
Acquiring material in public libraries is a core library activity to fulfill the unique needs of the reader's community. The present study aims to explore the trends of monograph acquisition in public libraries. The population consists of the four major public libraries of Lahore. A case study approach has been used to achieve the objectives of the study. Research is based on primarily the personal visits of the researcher to the acquisition departments of these libraries in order to collect data. Structured interviews were carried out with acquisition librarians to investigate the process of purchasing. The analysis of data reveals that a high ratio of Urdu language books has been purchased during the last decade, literature and religion being the major purchase area, whereas, art and architecture, pure sciences, and languages are the most neglected. The findings further revealed that the studied libraries have primarily been using traditional and informal techniques for acquiring material.
_eprint: https://doi.org/10.1080/14649055.2016.1170471
Keywords: Pakistan librarianship; acquisition trends; dept.ils; monograph acquisition; public libraries

Reading Trends of Youth in Pakistan: A Pilot Study - Soroya, Saira Hanif; Ameen, Kanwal (Pakistan Journal of Information Management and Libraries, 2016)
The present study, a part of researcher's Ph.D. project, aimed at exploring the reading trends of young Pakistani students (i.e., Generation Y: born during the 1980s and early 1990s, also known as internet generation), and the impact of digital media on their reading behavior. It was conducted as a pilot study on final year's master level students of the University of the Punjab. Quantitative research design, based on a survey was used. Convenient sampling technique was used to collect data from 50 students through questionnaire survey. It revealed that the students' reading behavior has been significantly changed during the last five years. Their overall reading time and digital reading time has been increased due to the availability of digital devices and digital reading material. The findings of this study are helpful in identifying the trends of reading behavior as well as in planning and designing library services with regard to the considering of the behavior of the students.
Keywords: dept.ils

Academic Integrity: Effects of Demographic Variables on Students’ Conduct - Soroya, Dr Muhammad Shahid; Hashmi, Dr Muhammad Amir; Soroya, Saira Hanif (South Asian Studies, 2020)
This study aimed to find out the effects of demographic variable i.e. gender, age, group of studies, GPA etc. on level of academic integrity among Pakistani students. The design of the study is quantitative in nature, in which the survey research method was employed to gather data from the respondents. A self-reported questionnaire was adapted on the basis of previously developed and validated questionnaire, with the consent of the authors. The developed scale was validated with the help of experts and pilot tested. Multilevel stratified convenience sampling technique was used to collect data from 4 provinces and federal area of Pakistan. The collected data was analyzed by using SPSS 16.0 version
Number: 2
Keywords: dept.ils

Application of marketing approach in academic libraries: an exploratory study of Punjab University Libraries (PULs) - Soroya, Saira Hanif; Ameen, Kanwal (Pakistan Library & Information Science Journal, 2017)
Keywords: dept.ils

What do they want? Millennials and role of libraries in Pakistan - Soroya, Saira Hanif; Ameen, Kanwal (The Journal of Academic Librarianship, 2018)
The present study is aimed at determining the future role of libraries in Pakistan as perceived by the Millennials (people born during the 1980's and late 1990's) considering the current ongoing digital development. The quantitative research design, based on survey has been used for the study. The population consisted of students from large and medium sized general universities of Lahore, Pakistan. Stratified purposive sampling technique was carried out to select the pool of the subjects e. A self-constructed and validated instrument was used to collect data. The collected data was analyzed using SPSS (16.0). The results revealed that Millennials want future libraries to allow easy access to a wide range of reading material in both print and digital form. They want to be able to round the clock access to electronic and print resources.
Keywords: 21st century library users; Future role of libraries; Millennials; Pakistan; dept.ils

Users' Satisfaction as a Valid Measure for Information Resources: A Case of Public Libraries - Bashir, Faiza, Saira Hanif, Soroya; Khanum, Almas (Journal of Library Administration, 2018)
The mission of public libraries is to serve the unique needs of their local communities. Public library User's play a very vital role in the development of these libraries by suggesting or recommending additions to the collection. This study aims to evaluate the satisfaction of users with the quality and quantity of library collection. A self structured questionnaire based on open and close ended question was constructed. A purposive sample of one hundred users was selected. The data were qualitatively analyzed using a thematic approach. Positive opinion observed related to the library response towards the suggested titles. Almost half the population of respondents was satisfied with the availability of their suggested titles in library. Most of them were dissatisfied regarding the maintenance of equal collection of books and they are not encouraged by the library staff during the books suggestion process. It concludes that there is a need to evaluate the existing library collections.
_eprint: https://doi.org/10.1080/01930826.2018.1436799
Keywords: dept.ils; information quality; information resources; public libraries; user satisfaction

Do We Deliver What They Expect? Finding the Gap Between Users' Expected and Currently Received Library Services. - Ara, Mehvish; Soroya, Saira Hanif (Pakistan Library & Information Science Journal, 2018)
This research aims to assess tire service quality of public libraries of Lahore by evaluating the disparities between the users' expectation and currently received services. The survey method based on questionnaire was used. Four of the largest libraries in Lahore, in terms of services, collection and other facilities, were the population of the study. A sample of four hundred library users was selected with one hundred library users for each library based on convenience sampling. A modified LibQUAL+ tool was adopted to collect the data. The findings revealed that users have very high expectations regarding the accessibility of library's electronic resources from home or office, library website, printed material, availability of electronic information resource, modem equipment, tools that allow the users to find the material themselves, and provision of the information in an easy manner. The findings are helpful for public libraries' authorities to redcsign/upgradc the quality of library services, policies and procedures according to users' expectations and requirements.
Keywords: ACCESS control; INTERNET access for library users; LAHORE (Pakistan); LIBRARY public services; LIBRARY records; Libraries; Libraries and Archives; PUBLIC libraries; dept.ils

Embracing the metaverse: a survey of virtual reality and augmented reality practices at the United States’ top one hundred university libraries - Guo, Yajun; Li, Shuai; Zhang, Xindi; Fu, Yiyang; Yuan, Yiming; Liu, Yanquan (College & Research Libraries, 2024)
The purpose of this study is to learn more about virtual reality (VR) and augmented reality (AR) practices at the United States’ top one hundred university libraries, as well as how they are engaging with the metaverse. We conducted qualitative and descriptive analysis on the websites of the top one hundred university libraries in the United States to determine the application fields and application proportions of VR and AR technologies and found good practice examples of using VR and AR technologies in this field. The findings show that 86 percent of the top one hundred US university libraries have implemented VR and AR technologies, with practice areas focused on: VR/AR studio and VR/AR makerspace; immersive learning services and virtual exhibitions/conference services; visual geographic information system and VR navigation services; virtual reading services and visual retrieval services; and VR reference services. The study provides university library administrators and professionals with the most up-to-date information and best practices of VR and AR engagement areas and the proportion of use, which can aid in the development of strategies to leverage VR and AR technologies to improve patron service and embrace the metaverse for the communities they serve.
Number: 7
Keywords: Metaverse；Virtual reality；Augmented reality；University Library；America；Survey; dept.ils; peer-reviewed

Role of Pakistani e-libraries in promoting health awareness for the attainment of Sustainable Development Goal-3 - Soroya, S.H.; Sharif, A.; Faiola, A. (Health Information and Libraries Journal, 2024)
Background: Pakistan is a densely populated South Asian country. It is facing numerous health challenges, as well as problems of the digital divide. The government of Pakistan established e-libraries as a pilot project in 2018. These libraries are functioning through community centers/public libraries in the largest province of the country. Objective: This paper examines the role of Pakistani e-libraries in creating health awareness and providing health information to the public. Methods: The qualitative research design was based on focus group discussions with the head librarians of all 13 of the 20 e-libraries contacted. Results: The findings revealed that e-libraries actively create health-related awareness and connect the public to health advisors. The e-libraries were engaged in four types of health-related activities (seminars, awareness campaigns, open health camps, and special health day celebrations) with high attendance from the public. Attendees of these programs returned to librarians with additional health-related queries. Conclusions: The study suggests a need for more liaison between the community and local healthcare institutions. This approach can make these programs more effective in helping individuals manage their health. The results of this study can serve as a useful guide for other developing nations in developing similar services. © 2024 Health Libraries Group.
Keywords: Asia; dept.ils; developing economies; digital information resources; health disparities; information services; peer-reviewed; public health; public libraries; south

Mobilization in US Top University Libraries/美国高校图书馆移动服务现状调查与分析 - Yang, Q.; Liu, Y.Q. (Library & Information/图书与情报, 2015)
Keywords: dept.ils

The Latest Study of Workplace Bullying and Anti-Bullying in American Libraries/美国图书馆工作场所欺凌和反欺凌现状最新调研 - He, J; Wang, Y; Liu, Y. Q. (Library & Information/图书与情报, 2015)
Keywords: dept.ils

Anti-fraud schema system for identification and prevention of fraud behaviors in E-commerce services - Yang, Qinghong; Wei, Xing; Hu, Xiangquan; QuanLiu, Yan (Global Journal of Computer Science and Technology, 2016)
Keywords: dept.ils

Service Mode of Smart Recommendation Based on Knowledge Discovery/基于知识挖掘的图书馆智慧推荐服务模式 - Wang, Y.; Dong, X.; Liu, Y. Q. (Research on Library Science/图书馆学研究, 2018)

Multimedia Design & HCI in Libraries - Liu, Dr Yan Quan (2016)
The primary purpose of this book is to help students understand the principles of multimedia interface design to develop essential skills. The underlying philosophy of the approach of this text is that concepts are learned and remembered better when learned in a real work environment.
Keywords: dept.ils

Readiness of Pakistani journals for open access publishing - Raza, M.Z.; Rafiq, M.; Soroya, S.H. (Electronic Library, 2024)
Purpose: This study was designed to discover the readiness of the higher education commission (HEC)-recognized journals of Pakistan in terms of human, financial and technological resources, technical expertise, institutional support, availability of open access (OA) policy, availability of guidance and training, willingness, motivation and so on for OA journal publishing and to expose the challenges in OA journal publishing. Design/methodology/approach: A quantitative research approach was used and a structured questionnaire was developed to meet the objectives of this study. A survey method was used to collect data from the editors of all 329 HEC-recognized journals in Pakistan. Findings: The respondents of all the HEC-recognized journals of Pakistan are neutral and are not of the view that they have sufficient financial, human, technological/infrastructural resources and technical expertise to continue/initiate an OA journal publishing. ‘No academic reward’; and ‘no monetary reward for the editorial staff’ are both enormous challenges for OA journal publishing. The perceived challenges of OA have a negative impact on readiness for OA publishing. The readiness level of the respondents of the OA journals is higher as compared to the readiness level of the respondents of non-OA journals. Research limitations/implications: This study covered the lists of HEC-recognized journals of 2019. More studies may be conducted based on updated lists of HEC-recognized journals. Qualitative studies may also be conducted to discover the readiness of the HEC-recognized journals of Pakistan for OA journal publishing. Originality/value: This study is the first comprehensive study on this phenomenon and is an effort to fill this gap to invigorate scholarly literature. It may attract the attention of policymakers, funding bodies, parent institutions of the journals and the HEC regarding the readiness of journals in terms of financial, human, technological/infrastructural resources, technical expertise of the journals and challenges of journals to prompt the OA journal publishing paradigm. © 2024, Emerald Publishing Limited.
Keywords: Challenges; Editors; Journal publishing; Journals; Open access; Pakistan; Readiness; dept.ils

Exploring the nexus: homeschooling and library engagement in Connecticut - Murtha, Helene R.; Schofield, Cindy K. (Public Library Quarterly, 2024)
In the dynamic landscape of education, homeschooling continues to offer a compelling alternative to traditional schooling. Homeschool numbers surged through the pandemic and have not decreased to pre-pandemic levels. This study examines the shared connections between homeschooled families in Connecticut and local public libraries by looking at how home educators use library resources and participate in library programming; and examining how Connecticut libraries perceive and respond to the diverse needs of homeschooling communities. Based on 2 Connecticut statewide surveys, one sent to public librarians and another to homeschoolers, the study sought to identify areas of strengths, weaknesses and disconnects in the homeschool community and public library relationships in Connecticut. Both qualitative and quantitative data was collected and reviewed to identify potential improvements to the evolving role of libraries in supporting alternative education pathways, and the potential for an infusion of public library support from the homeschool community.
_eprint: https://doi.org/10.1080/01616846.2024.2375173
Keywords: Homeschooling; dept.ils; education resources; libraries; peer-reviewed; public libraries; special populations

ADA digital accessibility on academic library websites - Liu, Yan Quan; Bielefield, Arlene; Beckwith, Jennifer (College & Research Libraries, 2024)
Studying ADA accessibility at library websites of top universities selected from the U.S. News and World Report, the authors used WAVE and AChecker to assess data in compliance with WCAG 2.0 standards. Almost 8 out of 10 public university academic libraries reported accessibility errors as one of the major findings. Low color contrast was becoming a more commonly occurring accessibility issue, making it difficult for people with vision impairments to perceive the color of the image. The outcomes of the study suggest that academic libraries around the world should continue improving their website accessibility.
Keywords: SCSU-student; dept.ils; peer-reviewed

Assessing the impact of health information orientation and health information literacy on patients’ engagement with health information - Hashmi, Ferhana Saeed; Soroya, Saira Hanif; Mahmood, Khalid (Journal of Information Science, 2024)
Health information engagement can help individuals to find and use reliable sources of health information to make informed decisions about their health. This helps to improve their health outcomes and prevent unnecessary healthcare costs. Drawing upon the cognitive behavioural theory, this pilot study postulated a model to understand that the consequences of information orientation in terms of information engagement (behaviour), information literacy (cognition) and information avoidance (behaviour) in post-COVID era under health context. Furthermore, the moderation effects of health information literacy (HIL) are also calculated in managing health information avoidance beahvior. This pilot study is conducted in the context of social media exposure to health information by diabetic patients in Pakistani community. The proposed model was tested using Partial Lease Square Structural Equational Modelling (PLS-SEM). The data were collected from 166 diabetic patients (active social media users) through a survey. The study findings suggest that health information orientation on social media leads to HIL and engagement. Whereas, it has significant negative impact towards health information avoidance behaviour. Furthermore, HIL significantly increases health information engagement of diabetic patients. Also, HIL moderates the relationship between health information orientation and information engagement positively, whereas between health information orientation and health information avoidance negatively.
Keywords: dept.ils; peer-reviewed

Core Competencies of Digital Humanities Librarianship in Academic Libraries / 美国学术图书馆数字人文图书馆员职业核心竞争力探究 - Li, G; Niu, Z.; Liu, Y. Q. (Library & Information, 2020)
Keywords: dept.ils; ⛔ No DOI found

Collaborative Efforts of U.S. School and Public Libraries on Reading Programs / 美国中小学与公共图书馆阅读推广合作模式及成功案例纵析 - Liang, Z; Liu (Library Development, 2020)
Keywords: dept.ils; ⛔ No DOI found

Analysis on Research Process and Characteristics of Technology Architecture of Digital Library - Huang, G.; Zheng, X.; Liu, Y. Q. (Digital Library Forum, 2021)
Keywords: dept.ils; ⛔ No DOI found

Research on Key Quality Issues of Government Open Data Based on IPA Analysis - Zuying, Mo; Hou Zheng, LiuYanquan (Information and Documentation Services, 2021)
Keywords: dept.ils; ⛔ No DOI found

Surfing the World of Knowledge: Analytical Case Studies of Digital Liberties in the United States - Liu, Dr Yan Quan (Independently published, 2021)
This work compiles a database that provides analytical case studies of typical digital libraries as an enhancement for educating and learning to meet the needs of students, librarians, scholars, and those who are interested in this resource.
Keywords: dept.ils

圖書館智慧服務: 基於知識挖掘與推薦系統的模式研究: Research of Library's Smart Service, Derived from Recommender Systems and Knowledge Discoveries - Quan, 刘燕权 Liu Yan; Yingchun, 王颖纯 Wang (Nook Digital LLC by Barnes & Noble®, 2022)
本書內容包括：智慧圖書館、知識服務、移動服務、推薦系統、無線射頻技術、學科及學術資源服務等關於中國與美國信息技術、知識管理和學科拓展。 本書可作為大中專信息管理學院、圖書館學院、軟件學院、管理學院，及所有相關專業的本科生、碩士生、博士生和教師等的專業教材或教學參考書。亦可作為計算機、圖書情報、信息管理，網絡文化教育等領域的研究人員和工程技術人員、管理人員、服務人員的信息參考資料。作為大學圖書館，公共圖書館，專業圖書館，各類信息中心，IT與網絡公司等機構收藏本圖書，為開展智慧服務提供借鑒參考。本書也可為信息資源管理相關行政部門實際工作提供政策建議，為大眾提供各類知識閱讀。
Keywords: dept.ils

From information seeking to information avoidance: Understanding the health information behavior during a global health crisis - Soroya, Saira Hanif; Farooq, Ali; Mahmood, Khalid; Isoaho, Jouni; Zara, Shan-e (Information Processing & Management, 2021)
Individuals seek information for informed decision-making, and they consult a variety of information sources nowadays. However, studies show that information from multiple sources can lead to information overload, which then creates negative psychological and behavioral responses. Drawing on the Stimulus-Organism-Response (S-O-R) framework, we propose a model to understand the effect of information seeking, information sources, and information overload (Stimuli) on information anxiety (psychological organism), and consequent behavioral response, information avoidance during the global health crisis (COVID-19). The proposed model was tested using partial least square structural equation modeling (PLS-SEM) for which data were collected from 321 Finnish adults using an online survey. People found to seek information from traditional sources such as mass media, print media, and online sources such as official websites and websites of newspapers and forums. Social media and personal networks were not the preferred sources. On the other hand, among different information sources, social media exposure has a significant relationship with information overload as well as information anxiety. Besides, information overload also predicted information anxiety, which further resulted in information avoidance.
Keywords: COVID-19; Information anxiety; Information avoidance; Information overload; Information seeking; dept.ils

A Study of the Deployment of Institutional Repositories in Colleges and Universities in Connecticut - Clarke, Christopher D.; Kim, Hak Joon (Practical Academic Librarianship: The International Journal of the SLA Academic Division, 2023)
In the past several years, many colleges and universities have developed institutional repositories as a means of highlighting the research and scholarship conducted at their institution as well as a means of combating the current publication model. Past studies have concentrated on growth in the total number of repositories, but none has looked at how the number of repositories in a particular region compares to those institutions without a repository. The primary purposes of this study were to find out how many colleges and universities in Connecticut have developed institutional repositories and how they have used these institutional repositories. Overall, this study revealed that less than a third of the academic institutions in Connecticut have institutional repositories. These repositories are most frequently found in the state sponsored universities and the independent, nonprofit schools. On the other hand, none of the community colleges, which constitute one of the largest proportion of schools in the state behind independent, nonprofits, has a repository. A vast majority of the repositories are registered with OpenDOAR, and nearly all of them use Digital Commons as their platform. The two most popular types of content found in Connecticut institutional repositories are journal articles and theses & dissertations.
Number: 1
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Scholarly Use of Electronic Resources: A Study of Citations and References Cited in Electronic Journal Articles. - Kim, Hak Joon (2009)
A study was conducted using 2,734 citations and references to electronic resources cited in 94 scholarly and peer reviewed ejournals published between 2005 and 2008. Study illustrated problems that occur when users attempt to access e-sources cited in e-journal articles.
Keywords: dept.ils; faculty_collection; sabbatical_report

Digital Libraries, Its Theory and Practices. - Liu, Yan Quan (2009)
Thirteen chapters and 47 sections of the book"Digital libraries, its theory and practices" were worked on and the book is ready to send to the publisher. Did a paper that was accepted by the journal Library Hi Tech. Visited China and gave 2 seminars in 2 universities in China.
Keywords: dept.ils; faculty_collection; sabbatical_report

Storytelling: Interdisciplinary Applications for the Elementary Curriculum. - Nowlan, Gwendolyn (2002)
Keywords: dept.ils; faculty_collection; sabbatical_report

Needs Assessment Survey Instrument to Identify Library Support Needs for on-Line Master of Library Science Students at Southern Connecticut Sate University. - Okobi, Elsie Rogers Halliday (2002)
Keywords: dept.ils; faculty_collection; sabbatical_report

American Encounters with Nazism: Sources of Early Experiences with the Hitler Movement. - Triolo, Victor (Spring;Library Science., 1997)
Keywords: dept.ils; faculty_collection; sabbatical_report

Incorporation of Pome Fruit Germplasm Inventory into the Grin Database System. - Triolo, Victor (1994)
Keywords: dept.ils; faculty_collection; sabbatical_report

Film Quotations; 11,000 Lines Spoken on Screen. - Nowlan, Gwendolyn Wright (1993)
Keywords: dept.ils; faculty_collection; sabbatical_report

Doctoral Program. - Disbrow, Nancy (1990)
Keywords: dept.ils; faculty_collection; sabbatical_report

A Dictionary of Quotations and Proverbs About Cats and Dogs - Nowlan, Robert A.; Nowlan, Gwendolyn Wright (McFarland, 2001)
Keywords: Cats; Quotations; maxims; etc; Quotations; maxims; etc; Dogs; dept.ils; dept.mat; faculty_collection

A Dictionary of Quotations About Communication - Nowlan, Robert A.; Nowlan, Gwendolyn Wright (McFarland, 2000)
Keywords: Quotations; Quotations; English; dept.ils; dept.mat; faculty_collection

We'll Always Have Paris: The Definitive Guide to Great Lines from the Movies - Nowlan, Robert A.; Nowlan, Gwendolyn Wright (HarperCollins Publishers, 1995)
Keywords: Motion pictures; Quotations; maxims; etc; dept.ils; dept.mat; faculty_collection

The Films of the Eighties: A Complete, Qualitative Filmography to Over 3400 Feature-Length English Language Films, Theatrical and Video-Only, Released Between January 1, 1980, and December 31, 1989 - Nowlan, Robert A.; Nowlan, Gwendolyn Wright (McFarland & Co., 1991)
Keywords: Catalogs; Motion pictures; dept.ils; dept.mat; faculty_collection

Library Science Research, 1974-1979 - Magnotti, Shirley (Whitson Pub. Co., 1982)
Keywords: Bibliography; Bibliography; Dissertations; Academic; Canada; Library science; United States; dept.ils; faculty_collection

Master's Theses in Library Science, 1970-1974 - Magnotti, Shirley (Whitston Pub. Co., 1976)
Keywords: Bibliography; Bibliography; Dissertations; Academic; Canada; Library science; United States; dept.ils; faculty_collection

Ehanna Woyakapi; History and Culture of the Sisseton Wahpeton Sioux Tribe of South Dakota - Blackthunder, Elijah; Johnson, Norma; Pronovost, Muriel; O'Connor, Larry (Sisseton Wahpeton Sioux Tribe, 1975)
Keywords: History; History; Wahpeton Indians; Sisseton Indians; dept.ils; faculty_collection

Empirical Research for Information Professionals - Liu, Yan Quan (Createspace, 2019)
A collection of empirical research published by Dr. yan Quan Liu and his reasearch teams in the field of information and library science for the 21st-century readers. - Back cover.
Keywords: Case studies; Library science; Research; Library science; dept.ils; faculty_collection

Information Science and Technology: An Introduction for Librarians (course Pack, 2nd Version) - Liu, Yan Quan (Create Space : Yan Quan Liu, 2018)
Keywords: Information science; Information technology; Information and Library Science; dept.ils; faculty_collection

Library Services for Mobile Users: A Library in the Palm of Your Hand - Liu, Yan Quan (CreateSpace, 2018)
This books is a print version of the online course ILS 440 Information Service Technology offered at Southern Connecticut State University. The course content includes the instructor's lecture notes, assignment instructions, assigned readings, discussions and coursework from students in the classes.
Keywords: Library applications; Public services (Libraries); Mobile communication systems; Technological innovations; dept.ils; faculty_collection

Transforming Library Service for the 21st Century User - Liu, Yan Quan (Createspace, 2018)
This book is a print version of the online course ILS508 User Services. The course content includes the instructor's lecture notes, assignment instructions, assigned readings, discussions an coursework from the students in the classes.
Keywords: Public services (Libraries); dept.ils; faculty_collection

Digital Libraries in Theory and Practices - Liu, Yan Quan (CreateSpace Independent Publishing Platform, 2016)
Keywords: Information storage and retrieval systems; dept.ils; faculty_collection

Library Services for Adults in the 21st Century - Okobi, Elsie A. Rogers Halliday (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2014)
"Develop the competencies needed to provide effective adult services in modern public libraries with this comprehensive guidebook"–
Keywords: Adult services in public libraries; United States; United States; Libraries and adult education; United States; Libraries and community; United States; Public services (Libraries); dept.ils; faculty_collection

Shu zi zhi shi bao ku zong lan: mei guo shu zi tu shu guan an li jing xi = Surfing the world of knowledge : analytical case studies of digital liberties [libraries] in the United States - 刘燕权; Liu, Yan Quan (Hai yang chu ban she, 2014)
Keywords: Digital libraries; United States; dept.ils; faculty_collection

International and Comparative Studies in Information and Library Science: A Focus on the United States and Asian Countries - Liu, Yan Quan; Cheng, Xiaojun (Scarecrow Press, 2008)
Keywords: Asia; Asia; Information science; Comparative librarianship; International librarianship; Library science; United States; Information science; United States; Library science; dept.ils; faculty_collection

Exhibits in Libraries: A Practical Guide - Brown, Mary E.; Power, Rebecca (McFarland & Co., 2006)
"Library exhibits can inspire and educate, stimulate an interest that can be explored in a book, or attract visitors who otherwise wouldn't stop by. Displays are an opportunity to put a creative foot forward or help patrons navigate the facility. This "how-to" includes everything a librarian needs to know to put on an exhibit"–Provided by publisher.
Keywords: Handbooks; manuals; etc; Library exhibits; dept.ils; faculty_collection

Libraries Designed for Users: A 21st Century Guide - Lushington, Nolan (Neal-Schuman Publishers, Neal-Schuman, 2002)
Keywords: Library buildings; Planning; Library architecture; Libraries; Space utilization; dept.ils; faculty_collection

Interpreting and Negotiating Licensing Agreements: A Guidebook for the Library, Research, and Teaching Professions - Bielefield, Arlene; Cheeseman, Lawrence (Neal-Schuman Publishers, 1999)
Keywords: Handbooks; manuals; etc; Handbooks; manuals; etc; Teachers; License agreements; Popular works; Librarians; United States; dept.ils; faculty_collection

The School Library Media Center - Prostano, Emanuel T.; Prostano, Joyce S. (Libraries Unlimited, 1999)
Keywords: School libraries; United States; United States; Instructional materials centers; dept.ils; faculty_collection

How to Use the Library: A Reference and Assignment Guide for Students - Ferro, Frank; Lushington, Nolan (Greenwood Press, 1998)
Keywords: Bibliography; Catalogs; Juvenile literature; Juvenile literature; Library research; Juvenile literature; Reference sources; Reference books; United States; dept.ils; faculty_collection

Technology and Copyright Law: A Guidebook for the Library, Research, and Teaching Professions - Bielefield, Arlene; Cheeseman, Lawrence (Neal-Schuman Publishers, 1997)
"Explains the intent of copyright law, how it developed, and where it is headed; provides guidance for making copyright decisions; and discusses the electronic classroom and international copyright agreements."
Keywords: Fair use (Copyright); Law and legislation; United States; United States; Information services; United States; Library legislation; dept.ils; faculty_collection

Library Patrons and the Law - Bielefield, Arlene; Cheeseman, Lawrence (Neal-Schuman Publishers, 1995)
Keywords: Censorship; Library legislation; United States; United States; Civil rights; United States; Libraries; United States; Privacy; Right of; dept.ils; faculty_collection

Maintaining the Privacy of Library Records: A Handbook and Guide - Bielefield, Arlene; Cheeseman, Lawrence (Neal-Schuman Publishers, 1994)
Keywords: Confidential communications; Library records; United States; dept.ils; faculty_collection

Libraries & Copyright Law - Bielefield, Arlene; Cheeseman, Lawrence (Neal-Schuman Publishers, 1993)
Keywords: Fair use (Copyright); Photocopying; United States; United States; Photocopying services in libraries; dept.ils; faculty_collection

Library Employment Within the Law - Bielefield, Arlene; Cheeseman, Lawrence (Neal-Schuman Publishers, 1993)
Keywords: Legal status; laws; etc.; Librarians; United States; United States; Library employees; dept.ils; faculty_collection

Feminist Thought in American Librarianship - Baum, Christina D. (McFarland, 1992)
Keywords: Social aspects; United States; United States; Feminism; United States; Libraries and society; United States; Library administration; United States; Library science; United States; Women librarians; Women in library science; dept.ils; faculty_collection

An Introduction to Using the Internet at Southern Connecticut State University - Bretthauer, David; Drew, Christine (1992)
Keywords: dept.ils; faculty_collection

The Connecticut Legal Research Handbook - Cheeseman, Lawrence; Bielefield, Arlene G. (Connecticut Law Book Co., 1992)
Keywords: Connecticut; Handbooks; manuals; etc; Legal research; dept.ils; faculty_collection

Evaluating Library Buildings: Principles and Procedures for Post-Occupancy Evaluation - Kusack, James M. (Connecticut State Library, 1991)
Book Title: Evaluating library buildings : principles and procedures for post-occupancy evaluation Place: Hartford, Conn.
Keywords: Evaluation; Library architecture; Library buildings; United States; dept.ils; faculty_collection

The Design and Evaluation of Public Library Buildings - Lushington, Nolan; Kusack, James M. (Library Professional Publications, 1991)
Keywords: Evaluation; Library buildings; Library architecture; Public libraries; dept.ils; faculty_collection

Educators Guide to Patents and Inventions - Prostano, Emanuel T.; Prostano, Joyce S. (In-Time Publications, 1990)
Keywords: Handbooks; manuals; etc; Patents; dept.ils; faculty_collection

School Library Media Programs: Success in the 90's - Prostano, Emanuel T.; Prostano, Joyce S. (In-Time Publications, 1989)
Keywords: School libraries; Media programs (Education); dept.ils; faculty_collection

The School Library Media Center - Prostano, Emanuel T.; Prostano, Joyce S. (Libraries Unlimited, 1987)
Keywords: School libraries; dept.ils; faculty_collection

Unions for Academic Library Support Staff: Impact on Workers and the Workplace. - Kusack, James M. (1986)
Keywords: Administration; Libraries and labor unions; College employees; Labor unions; Library employees; United States; United States; Academic libraries; United States; Collective bargaining; United States; Labor unions; dept.ils; faculty_collection

The Basic Business Library: Core Resources - Schlessinger, Bernard S. (Oryx Press, 1983)
Keywords: Bibliography; Bibliography; Business; Bibliography; Business libraries; Business libraries; Business; Reference books; dept.ils; faculty_collection

Scientific Management of Library Operations - Dougherty, Richard M.; Heinritz, Fred John (Scarecrow Press, 1982)
Keywords: Library administration; dept.ils; faculty_collection

The School Library Media Center - Prostano, Emanuel T.; Prostano, Joyce S. (Libraries Unlimited, 1982)
Keywords: School libraries; United States; United States; Instructional materials centers; dept.ils

The School Library Media Center - Prostano, Emanuel T.; Prostano, Joyce S. (Libraries Unlimited, 1977)
Keywords: School libraries; United States; United States; Instructional materials centers; dept.ils; faculty_collection

Andover in the American Revolution: A New England Town in a Period of Crisis, 1763-1790 - Harris, Edward Moseley (Walsworth Pub. Co., 1976)
Keywords: 18th century; Andover (Mass.); Biography; Andover (Mass.); Campaigns; Andover (Mass.); Genealogy; History; Revolution; 1775-1783; United States; dept.ils

School Media Programs: Case Studies in Management, - Prostano, Emanuel T. (Scarecrow Press, 1974)
Keywords: Administration; Case studies; Case studies; Media programs (Education); School libraries; dept.ils; faculty_collection

Law Enforcement; a Selective Bibliography - Prostano, Emanuel T.; Piccirillo, Martin L. (Libraries Unlimited, 1974)
Keywords: Bibliography; Bibliography; Crime; Bibliography; Criminal justice; Administration of; Bibliography; Police; Law enforcement; dept.ils; faculty_collection

Audiovisual Media and Libraries; Selected Readings. - Prostano, Emanuel T. (Libraries Unlimited, 1972)
Keywords: Audio-visual library service; dept.ils; faculty_collection

Users and Uses of the New Haven Free Public Library, July, 1972; a Survey - Schlessinger, Bernard S. (1972)
Keywords: New Haven Free Public Library; dept.ils; faculty_collection

The School Library Media Center - Prostano, Emanuel T.; Prostano, Joyce S. (Libraries Unlimited, 1971)
Keywords: School libraries; United States; United States; Instructional materials centers; dept.ils; faculty_collection

School Media Programs: Case Studies in Management, - Prostano, Emanuel T. (Scarecrow Press, 1970)
Keywords: Administration; Case studies; Case studies; Library administration; Case studies; Media programs (Education); School libraries; dept.ils; faculty_collection

Readings About Children's Literature. - Robinson, Evelyn Rose (D. McKay Co., 1966)
Keywords: Books and reading; Children's literature; History and criticism; Children; dept.ils; faculty_collection

An Analysis of School Library Resources in Connecticut as Compared to National Standards, 1960-1961. - Prostano, Emanuel T. (University Microfilms, 1962)
Keywords: Connecticut; School libraries; dept.ils; faculty_collection

Academic pursuits and involvement in decision-making: study on the formation of U.S. university think tanks - Lyu, Qing; Bielefield, Arlene; Liu, Yan Quan (Administrative Sciences, 2023)
This paper analyzes the concept of think tanks and concludes that think tanks have three basic characteristics. Firstly, they are based on academic research, relatively independent operation, and aim to serve scientific decision-making. Taking Ivy League think tanks as an example, this paper provides a preliminary discussion of ways for think tanks to maintain the scientific nature of their research, maintain the independence of their operations, and disseminate research results to enhance their influence. It covers institutional mission, research team construction, institutional governance, fundraising, achievements and activities, and alumni networks. This paper proposes a framework of university think tank generation paths associated with the essential characteristics of think tanks. The paper points out that, as a research consulting organization grown out of universities, university think tanks must maintain the scientific nature and independence of research while providing support and services for decision-making. Only in this way can they truly serve scientific and democratic decision-making, gain the trust of the public and have a real lasting influence.
0 citations (Crossref) [2023-10-31] Number: 3
Keywords: American university affiliated think tank; characteristics of think tank; decision-making; dept.ils; peer-reviewed; the ivy league university; think tank operation mechanism

Services to mobile users: the best practice from the top-visited public libraries in the US - Liu, Yan Quan; Lewis, Sarah (Information Technology and Libraries, 2023)
Libraries are adapting to the changing times by providing mobile services. One hundred fifty-one libraries were chosen based on circulation, with at least one library or library system from each state, to explore the diverse services provided to mobile users across the United States. According to the data, mobile apps, mobile reference services, mobile library catalogs, and mobile printing are among public libraries’ most-frequently offered services, as determined by mobile visits, content analysis, and librarian survey responses. Every library examined had at least one mobile website, mobile catalog, mobile app, or webpage adapted for a mobile device. Following the COVID-19 outbreak, services such as mobile renewal, subscriber database access, mobile reservations, and the ability to interact with a librarian were expanded to allow better communication with customers—all from the comfort and safety of their own homes. Libraries are continually looking for innovative methods to assist their mobile customers as the world changes.
0 citations (Crossref) [2023-10-31] Number: 1
Keywords: Mobile Apps; Mobile services; Public Libraries; SCSU-student; Survey study; dept.ils; peer-reviewed

Contactless Services: A Survey of the Practices of Large Public Libraries in China - Guo, Y.; Yang, Z.; Yuan, Y.; Ma, H.; Liu, Y.Q. (Information Technology and Libraries, 2022)
Contactless services have become a common way for public libraries to provide services. As a result, the strategy used by public libraries in China will effectively stop the spread of epidemics caused by human touch and will serve as a model for other libraries throughout the world. The primary goal of this study is to gain a deeper understanding of the contactless service measures provided by large Chinese public libraries for users in the pandemic era, as well as the challenges and countermeasures for providing such services. The data for this study was obtained using a combination of website investigation, content analysis, and telephone interviews for an analytical survey study of 128 large public libraries in China. The study finds that touch-free information dissemination, remote resources use, no-touch interaction self-services, network services, online reference, and smart services without personal interactions are among the contactless services available in Chinese public libraries. Exploring the current state of contactless services in large public libraries in China will help to fill a need for empirical attention to contactless services in libraries and the public sector. Up-to-date information to assist libraries all over the world in improving their contactless services implementation and practices is provided. © 2022.
1 citations (Crossref) [2023-10-31]
Keywords: dept.ils; peer-reviewed

Symposium on Cooperative Efforts in Information Processing. Introduction - Schlessinger, B.S. (Journal of Chemical Documentation, 1973)
0 citations (Crossref) [2023-10-31]
Keywords: dept.ils

The Amount of Reading Material in Book Form Printed Yearly in the USSR and the USA - Vebra, G.I. (Libri, 1973)
1 citations (Crossref) [2023-10-31]
Keywords: dept.ils

Teaching scientific literature in the small college and university - Powell, A.; Schlessinger, B.S. (Journal of Chemical Education, 1971)
5 citations (Crossref) [2023-10-31]
Keywords: dept.ils

Symposium on Functions and Contributions of the Industrial Information Center - Schlessinger, B.S. (Journal of Chemical Documentation, 1971)
0 citations (Crossref) [2023-10-31]
Keywords: dept.ils

Trigant burrow and robert mearns yerkes the men and their papers - Stark, B.P. (Behavioral and Social Sciences Librarian, 1986)
Trigant Burrow and Robert Mearns Yerkes were two important behavioral scientists whose papers have recently been processed in Manuscripts and Archives, Yale University Library. Burrow was a pioneer American psychoanalyst and initiator of group analysis, while Yerkes was a prominent psychologist who is best known for his intelligence testing experiments in World War I and his studies of primate behavior. The paper discusses the lives and careers of both men; the research value of the two collections; the processing, arranging, and describing of the papers; and concludes with thoughts on access and the importance of finding aids to researchers and the institution that produces them. © 1986 by The Haworth Press, Inc.
0 citations (Crossref) [2023-10-31]
Keywords: dept.ils

The impact of local tape databases on the library: The M(I)das touch - Bakowski, V.B.; Moeckel, L.E. (Online (Wilton, Connecticut), 1990)
There is no abstract available for the item entitled The impact of local tape databases on the library: The M(I)das touch.
Keywords: dept.ils; ⛔ No DOI found

Planning more powerful ways to deliver information to the desktop - Dykman, E.K. (Online (Wilton, Connecticut), 1996)
Keywords: dept.ils; ⛔ No DOI found

We better get this party started! - Lavoie, L.; Markiewicz, J. (College and Undergraduate Libraries, 2006)
Each fall, the Tunxis Library hosts a party. Usually thematic, sometimes didactic, and always cerebral, the library uses the party to communicate our “party line” to the entire campus community: we are here to make your life easier. It's particularly effective when delivered at the start of the semester, before the unrelenting rhythm of classes, committee work, and meetings has begun. Showing the campus community that the library is here to support them is our core theme, wrapped in a party context. Our goal is to create a party that jump-starts the fall semester for everyone. In this article, we describe our most recent parties, focusing how we develop, plan, and execute these promotional initiatives, with little money, but plenty of creativity and teamwork. © 2005 by The Haworth Press, Inc. All rights reserved.
2 citations (Crossref) [2023-10-31]
Keywords: Community colleges; Library marketing; Library promotion; Parties; Teams; dept.ils

Evaluation of federated searching options for the school library - Abercrombie, S.E. (School Library Media Research, 2008)
Three hosted federated search tools, Follett One Search, Gale PowerSearch Plus, and WebFeat Express, were configured and implemented in a school library. Databases from five vendors and the OPAC were systematically searched. Federated search results were compared with each other and to the results of the same searches in the database's native interface to disclose differences in handling query syntax, searching, retrieval, browsing results, etc. Each product was easily configured, but none were capable of searching every database desired. Simpler Boolean queries are the most successful queries because of the underlying structure and differences of the databases, and the capabilities of certain products. Federated search products succeed in simplifying access to multiple database resources at school, but searching remains different from the familiar Web search engines in many ways. To become more Google-like, federated searching must be done against indexes built in advance instead of the current real-time searching method.
Keywords: dept.ils; ⛔ No DOI found

Citation searching: Search smarter & find more - Hammond, C.C.; Brown, S.W. (Computers in Libraries, 2008)
All in all, citation searching is a wonderful way to build a comprehensive body of knowledge. The databases allow you to follow a trail of cited references that weaves a web of information across the boundaries of time and subject limitations. It eliminates your need to know appropriate synonyms or subject-specific lingo in order to perform effective searches that yield inclusive results. Citation searching saves time while also increasing the likelihood that your search results will be appropriate for your needs. Citation searching is not just useful for librarians but for other searchers as well. If you need a comprehensive literature review - whether you're a librarian, faculty member, student, or scientist - you would benefit greatly from the capabilities of citation searching databases. The training program for citation searching at the University of Connecticut taught graduate students all these tricks and more. Students who attended our sessions now know how to do broad, interdisciplinary searches after they have searched their primary subject database. They also understand how to "chain" from the original article to the "backward" citations in that article and to the "forward" articles that cited the original. Finally, they see how they can use citation databases to find information about who's citing their articles, which they can use for job searching and grant proposals, promotion, and tenure. Try it yourself - you're sure to find something new!
Keywords: dept.ils; ⛔ No DOI found

Is data curation education at library and information science schools in North America adequate? - Harris-Pierce, R.L.; Liu, Y.Q. (New Library World, 2012)
Purpose: This study aims to present the results of a survey of library and information science (LIS) schools' websites used to determine if the number of data curation courses offered is adequate to address the needs of the so-called "data deluge". Many authors have identified a gap in the education of LIS students for data curation. Design/methodology/approach: This study surveyed the websites of LIS schools in North America to identify data curation courses. It reviewed and analyzed course descriptions, objectives and syllabi (when available) as well as compared course objectives, requirements, topics, assignments, and projects of the identified courses. Findings: Of the 52 LIS schools in North America's websites examined in this study, 16 institutions offered courses on data curation. The increase in the number of schools offering courses in data curation showed that LIS schools are responding to the demand for data curation professionals. More LIS schools need to add data curation to their curriculum. LIS schools currently offering data curation courses should continue to work together to determine the optimal course objectives and learning outcomes. Originality/value: Although there are several papers focused on particular data curation programs at a few universities, there are no papers that provide an overall view of the status of data curation education in higher education institutions today. This research will be of value and interest to LIS educators and professionals to determine if there is adequate education in place and to identify and evaluate the current state of data curation education. © Emerald Group Publishing Limited.
20 citations (Crossref) [2023-10-31]
Keywords: Digital curation; Digital curation education; Digital librarianship; Digital libraries; Education of information and library science; Information and library school; Information management; dept.ils

Social indexing: A solution to the challenges of current information organization - Choi, Y. (Libr. Inf. Sci., 2014)
Purpose - This chapter aims to discuss the issues associated with social indexing as a solution to the challenges of current information organization systems by investigating the quality and efficacy of social indexing. Design/methodology/approach - The chapter focuses on the study which compared indexing similarity between two professional groups and also compared social tagging and professional indexing. The study employed the method of the modified vector-based Indexing Consistency Density (ICD) with three different similarity measures: cosine similarity, dot product similarity, and Euclidean distance metric. Findings - The investigation of social indexing in comparison of professional indexing demonstrates that social tags are more accurate descriptions of resources and reflection of more current terminology than controlled vocabulary. Through the characteristics of social tagging discussed in this chapter, we have a clearer understanding of the extent to which social indexing can be used to replace and improve upon professional indexing. Research limitations/implications - As investment in professionally developed web directories diminishes, it becomes even more critical to understand the characteristics of social tagging and to obtain benefit from it. In future research, the examination of subjective tags needs to be conducted. A survey or user study on tagging behavior also would help to extend understanding of social indexing practices. © 2013 by Emerald Group Publishing Limited.
Journal Abbreviation: Libr. Inf. Sci. Pages: 135
Keywords: dept.ils

The information quest as resolution of uncertainty: Some approaches to the problem - Sieving, P.C. (Information Seeking and Communicating Behavior of Scientists and Engineers, 1991)
The ideal user of scientific and technical information: shall we design one? The positive personality traits one would wish for in a spouse would do nicely for a start: patient; thoughtful; caring; able to see our (the librarians') virtues through the fog of early-morning not yet-wakefulness or late evening exhaustion; able to communicate needs and wants clearly and without a lot of emotional overtones; willing to work hard to obtain desired results; and apprecia tive of what We (librarians) do. Add to this other talents which, while useful, are less often associated with marriage: the ability to understand and retain complex organizational details; patience with less-than-perfect systems; an intuitive understanding of how information is organized; and a sense of how best to cope with the inter-face between the deluge of possible information resources and the limited needs of one particular user (not to mention limited capacities for retaining and controlling that information flood once the gates are open). © 1991 by The Haworth Press, Inc. All rights reserved.
Journal Abbreviation: Inf. Seeking and Communicating Behavior of Scientists and Engineers
Keywords: dept.ils

Training the end user: The stanford university medical center experience - Linder, G.A.; Lenon, R.A.; Su, V.; Wible, J.G.; Stangl, P. (End User Searching in the Health Sciences, 1986)
The Lane Medical Library staff, working with a physician at Stanford University Medical Center, has developed a successful end user MEDLINE training program. 80th DIALOG and the National Library of Medicine’s (NLM) MEDLARS system are taught. Upon completion of the NLM course, students are eligible to receive academic credit and an NLM password. Several factors are identified as having been crucial to this success: (1) a strong working alliance between library staff and an enthusiastic physician, (2) early and ongoing support from influential leaders in the medical center, (3) minimization of barriers confronting potential end user searchers, and (4) strong emphasis on demonstration and hands-on practice. Costs and personnel support to achieve and maintain the program are discussed, and future plans outlined. © 1986 by The Haworth Press, Inc. All rights reserved.
Journal Abbreviation: End User Search. in the Health Sciences
Keywords: dept.ils

Exploring library core competencies: A text mining study of american library association’s job advertisements from 2006 through 2017: - Yang, Qinghong; Shi, Zehong; Liu, Yan Quan (Social Science Computer Review, 2021)
Are core competency requirements for relevant positions in the library shifting? Applying natural language processing techniques to understand the current market demand for core competencies, this study explores job advertisements issued by the American Library Association (ALA) from 2006 to 2017. Research reveals that the job demand continues to rise at a rate of 13% (2006–2017) and that the requirements for work experience are substantially extended, diversity of job titles becomes prevalent, and rich service experience and continuous lifelong learning skills are becoming more and more predominant for librarians. This analytical investigation informs the emerging demands in the American job market debriefing the prioritization and reprioritization of the current core competency requirements for ALA librarians. © The Author(s) 2021.
0 citations (Crossref) [2023-10-31]
Keywords: dept.ils; peer-reviewed

Bridging digital divides during COVID-19: Findings from the 2020-2021 connecticut state library digital inclusion survey - Real, Brian (Public Library Quarterly, 2021)
This article presents findings from the 2020–2021 Connecticut State Library Digital Inclusion Survey. The primary purpose of this study was to determine what actions public libraries in Connecticut are already taking to meet the digital inclusion needs of their communities and what information and assistance they need to better meet these goals. However, since this study was launched during the COVID-19 pandemic, the author customized numerous questions to focus on how public libraries have adjusted their operations when patrons have had limited access to library buildings. Responses from public library representatives throughout the state show that libraries have used tactics such as delivering previously in-person public programs through video conferencing formats and shifting portions of their physical materials budget to support digital items. © 2021 The Author(s). Published with license by Taylor & Francis Group, LLC.
11 citations (Crossref) [2023-10-31]
Keywords: dept.ils; peer-reviewed

Private post-secondary library websites and the ADA: compliancy and COVID-19 - Bielefield, Arlene; Liu, Yan Quan; Waimon, Victoria (Universal Access in the Information Society, 2023)
This study explores whether US post-secondary institutions (PPI) follow philosophies to foster inclusive communities, providing resources for those individuals with disabilities thrive socially, personally, and academically, while there have been no thorough studies conducted to determine web accessibility of the nation’s top-ranked PPI library webpages. Additionally, this study pioneers in comparison with the accessibility of PPI’s library homepages fighting COVID-19. The study evaluated the library homepages of the premium PPIs based on Money.com’s 2019 list of “The Best Colleges in America” via the WAVE web accessibility evaluation tool. The outcomes determined that most of the library homepages analyzed were littered with numerous errors, and the shift to online-based research in learning had no significant impact on the number of errors WAVE detected. The disconcerting findings of this study demonstrate the overall failure to recognize the importance of web accessibility or perhaps even the indifference toward accessibility on the part of the PPI community.
Keywords: ADA; Academic libraries; Accessibility; COVID-19; Disability; Overall failure; Philosophical aspects; Post-secondary institutions; Private colleges and universities; SCSU-student; Section 508; WAVE; WCAG; Web accessibility; Websites; dept.ils; peer-reviewed

Public library events: Who, what, where, when, and why? - Kukiolczynski, Katie Teresa; Liu, Yan Quan (Public Library Quarterly, 2021)
An explorative survey pertaining to organization and execution of programs and events offered in public libraries across Connecticut revealed that library programs have been steadily increasing in recent years, with most libraries providing one hundred or more programs a year. The types of programs that are most popular vary throughout the library’s open hours. Children’s programming appears to be more popular during the day while adult programming is more popular in the evening. Program popularity is based on grouping and continuous support from external partners. While this study confirmed that both library space and library staff sizes are adequate for programming, a further investigation would assert that this is the case within nationwide library programming.
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103569958
Keywords: Connecticut; Public libraries; dept.ils; library events; library programs; peer-reviewed

Using the Computer for Library Random Sample Selection - Heinritz, FJ (College & Research Libraries, 1979)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1979GY06400008
Keywords: dept.ils

Decision Tables - Tool for Librarians - Heinritz, FJ (Library Resources & Technical Services, 1978)
tex.unique-id: ISI:A1978EM07600004
Keywords: dept.ils; ⛔ No DOI found

Recommended Procedures for Internal Financial Auditing of University-Libraries - Kurth,wh, Zubatsky,ds - Heinritz, FJ (College & Research Libraries, 1978)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1978EJ86000025
Keywords: dept.ils

Rate of Growth for Library Collections - Heinritz, F (College & Research Libraries, 1974)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1974S674800002
Keywords: dept.ils

Analysis and Evaluation of Current Library Procedures - Heinritz, FJ (Library Trends, 1973)
tex.unique-id: ISI:A1973P828100006
Keywords: dept.ils; ⛔ No DOI found

Systematic Analysis of University Libraries - Application of Cost-Benefit Analysis to Mit Libraries - Raffel,ja and Shishko,r - Heinritz, FJ (Library Resources & Technical Services, 1970)
tex.unique-id: ISI:A1970H282100022
Keywords: dept.ils; ⛔ No DOI found

Theory and Practice in American-Medicine - Historical Studies from Journal of History of Medicine and Allied Sciences - Brieger,gh - Triolo, VA (Isis, 1978)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1978FN05600029
Keywords: dept.ils

Continuing-Education in Online Searching - Instructional Module for Special Librarians - Triolo, VA; Regazzi, JJ (Special Libraries, 1978)
tex.unique-id: ISI:A1978EW38300005
Keywords: dept.ils; ⛔ No DOI found

Big-City Police - Fogelson,rm - Levy, BN (Library Journal, 1977)
tex.unique-id: ISI:A1977DZ57800179
Keywords: dept.ils; ⛔ No DOI found

History of Public-Library in Brunswick, Maine - Helmreich,lr - Libbey, DC (Journal of Library History Philosophy and Comparative Librarianship, 1977)
tex.unique-id: ISI:A1977EC67200018
Keywords: dept.ils; ⛔ No DOI found

So Thats the Reason - Perrins, BC (RQ, 1967)
tex.unique-id: ISI:A1967ZY24300006
Keywords: dept.ils; ⛔ No DOI found

Myths, misconceptions and mistakes in collection development - Yesner, Bernice L. (Collection Management, 1985)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00224 tex.type: [object Object]
Keywords: dept.ils

Librarians Agreements - Bargaining for a Heterogeneous Profession - Weatherford,jw - Kusack, JM (Journal of Academic Librarianship, 1989)
tex.unique-id: ISI:A1989AJ83900012
Keywords: dept.ils; ⛔ No DOI found

Taken aback - Kusack, J (Wilson Library Bulletin, 1987)
tex.unique-id: ISI:A1987K534200002
Keywords: dept.ils; ⛔ No DOI found

Output measures and library space planning - Lushington, N. (Library Trends, 1987)
This article suggests that over the next decade library performance measures - such as output measures - can become the basis for library space planning programs that will determine the quantity and relative location of user hierarchies for each type of public service.
Keywords: dept.ils; ⛔ No DOI found

A longitudinal study of emotion expression and personality relations in early development - Abe, J.A.A.; Izard, C.E. (Journal of Personality and Social Psychology, 1999)
To investigate emotion expression and personality relations, the authors coded infants' full-face and component positive and negative expressions during Episodes 4 through 8 of the strange situation procedure at age 18 months and obtained maternal ratings of the 5-factor model of personality when children were 3.5 years old. Full-face negative expression was directly related to Neuroticism and inversely related to Agreeableness and Conscientiousness. By contrast, component positive expression showed the exact opposite pattern of relations. Full-face positive expression was positively correlated with Extraversion and Openness to Experience. These findings indicate that full-face and component expressions may index different intensities of emotions. Emotion expression and personality relations were not mediated by the security of attachment continuum or the emotional reactivity dichotomy derived from the attachment subclassifications.
58 citations (Crossref) [2023-10-31]
Keywords: *Emotions; *Personality; Age Factors; Child; Preschool; Emotions; Female; Humans; Longitudinal Studies; Male; Personality; age; article; dept.ils; dept.psy; emotion; female; human; longitudinal study; male; personality; preschool child

The developmental functions of emotions: An analysis in terms of differential emotions theory - Abe, J.A.A.; Izard, C.E. (Cognition and Emotion, 1999)
A substantial body of theoretical literature testifies to the evolutionary functions of emotions. Relatively little has been written about their developmental functions. This article discusses the developmental functions of emotions from the perspective of differential emotions theory (DET; Izard, 1977, 1991). According to DET, although all the emotions retain their adaptive and motivational functions across the lifespan, different sets of emotions may become relatively more prominent in the different stages of life as they serve stage-related developmental processes. In the first section, we present a brief overview of relevant aspects of the theory. In the second section, we discuss how emotions play a central role in helping the individual achieve developmental milestones and tasks during four major periods of life: Infancy, toddler through preschool years, middle to late childhood, and adolescence. The underlying thesis of this article is that emotions play a central role in stimulating social cognitive attainments at each stage of development. © 1999 Psychology Press Ltd.
69 citations (Crossref) [2023-10-31]
Keywords: dept.ils

Knowledge, concepts, and categories. - Brown, ME (Library & Information Science Research, 1999)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000079397400012
Keywords: dept.ils

Book Review: Electronic publishing and libraries. Planning for the impact and growth to 2003 - Brown,DJ - Brown, Mary E (Journal of the American Society for Information Science, 1997)
0 citations (Crossref) [2023-10-31] OCLC: 4650537768 Citation Key Alias: lens.org/107-477-196-608-69X, pop00100
Keywords: book.review; dept.ils

By any other name: Accounting for failure in the naming of subject categories - Brown, Mary E (Library & Information Science Research, 1995)
Research shows 65-80% of subject search terms fail to match the appropriate subject heading and one-third to one-half of subject searches result in no references being retrieved. In a cross-sectional study, 82 students (3rd grade through college) were presented complex concepts in a naming task. Concreteness, complexity, and syndeticity contributed significantly in explaining match-failure and predicting match-success. The likelihood of match-success following an initial failure is improved by manipulating the values of these three properties. Developmental trends which worked against match-success were observed. It is suggested that match-failure is a consequence of developmental naming patterns and that these patterns can be overcome through the use of metacognitive naming skills.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/058-254-372-457-138 tex.type: [object Object]
Keywords: dept.ils

To see or not to see - A study of video collection censorship in american public-libraries - Vroman, Deborah L. (RQ, 1995)
Citation Key Alias: vanfleetCurrentIssues1995 tex.unique-id: [object Object]
Keywords: dept.ils; ⛔ No DOI found

The information environment - a reader - walker,g - Kusack, J (Library Quarterly, 1993)
tex.unique-id: ISI:A1993KX91900016
Keywords: dept.ils; ⛔ No DOI found

A decision model for technical journal deselection with an experiment in biomedical communications - Triolo, Victor A; Bao, Dachun (Journal of the American Society for Information Science, 1993)
This report proposes a paradigm for technical journal deselection based on the Bradford Law of distribution, with a demonstration in biomedical communications illustrating various statistical derivations. The model employs the following operational prescriptives: (1) identification of fractional productivities in journal collections; (2) probability predictions for making successful retrievals of relevant items in any given productive fraction; (3) utilization by journal source language and origin; and (4) estimates of cost-efficiencies of searches made in print and machine-readable versions of serial publications. The results suggest that in approximately two out of three trials successful searches ('hits') are likely to be made in a `critical' core of any technical subject collection. The highest probability for retention resides in this portion, about 20% of the publications. We infer that substantial amounts of the remaining publications are candidates for deselection since their information content, as needed, may be captured more cost-effectively through electronic retrieval and document delivery access.
5 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1993KR97500003, lens.org/020-062-823-091-476 tex.type: [object Object]
Keywords: dept.ils

The light at the end of the carpal-tunnel - Kusack, JM (Library Journal, 1990)
tex.unique-id: ISI:A1990DN77000020
Keywords: dept.ils; ⛔ No DOI found

Gender distinctiveness, communicative competence, and the problem of gender judgments in computer-mediated communication - Sierpe, Eino (Computers in Human Behavior, 2005)
Despite persistent claims regarding the ability of text-based computer-mediated communication to neutralize gender identities, few researchers have worked on the problem of gender distinctiveness in textual production and interpretation, gender judgments, and more importantly, the role of gender in the process of impression formation in electronic communication. Against this background, the author addresses the theoretical aspects of gender in textual communication and places the problem of gender distinctiveness and gender judgments in CIVIC in the context of Hymes' model of communicative competence. He also isolates several variables worthy of investigation, namely, the provision of gender judgments, accuracy, and certainty. He then reconceptualizes the problem of gender distinctiveness and impression formation in CIVIC by bridging the gap between textual markedness and expectations. (C) 2003 Elsevier Ltd. All rights reserved.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/055-557-328-035-914 tex.type: [object Object]
Keywords: Communicative competence; Computer-mediated communication; Electronic communications; Formal languages; Gender judgments; Linguistics; Problem solving; Research; dept.ils; peer-reviewed

Power information user model presents worthy premise but flawed methodology (multiple letters) - Iwema, C.L.; Sathe, N.; Lee, P.; Giuse, N. (Journal of the Medical Library Association, 2005)
Keywords: Community-Institutional Relations; Health Education; Humans; Inservice Training; Models; Organizational; Research Design; Tennessee; dept.ils; health care personnel; information dissemination; letter; library; library science; medical informatics; medical information system; methodology; public health; research; ⛔ No DOI found

Distance education and the new MLS: The employer's perspective - Kim, Hak Joon; Kusack, James Michael (Journal of Education for Library and Information Science, 2005)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-066-399-143-203 tex.type: [object Object]
Keywords: dept.ils

The present and future of China's National Science and Technology Library - A new paradigm of sci-tech information resource sharing - Meng, Liansheng; Liu, Yan Quan (New Library World, 2005)
Purpose - The purpose of this case study is to explore the construction pattern and issues involved with the development of the National Science and Technology Library (NSTL) in China. Design/methodology/approach - This study was conducted through an analytical evaluation of the historical development of scientific and technological information sharing among libraries and information centers and issues around construction of the NSTL. Findings - Since the establishment of its network service system at the end of 2000, the NSTL has made rapid progress in constructing a sci-tech information resource sharing system and offering web-based information services to the patrons of scientific and technical communities all over China. Originality/value - This paper is the first exploration that brings to the forefront the foundational background of the NSTL, the characteristics of its organizational structure, the functions of its service, and the tentative plan to increase its accessibility and usability. Symptomatic of the function of the NSTL constructing pattern will hopefully shed light not only to the reformation of the Chinese sci-tech information management system, but also to the development of scientific digital libraries in the world. © Emerald Group Publishing Limited.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-870-955-879-723 tex.type: [object Object]
Keywords: China; Digital libraries; Document management; Information services; National libraries; Worldwide web; dept.ils

Library preservation in Russia: hope and despair on the edge of the technological revolution - Popova‐Gosart, Ulia (Library Management, 2004)
The paper discusses the state of library preservation as the main problem of library management in Russia during the times of transition to digital environments. Today, Russia's extensive library system is undergoing a paradigm change toward the implementation of information technology (IT) to develop public access to information, that is perceived to be vital for the growth of the country. The first principal projects to elevate Russia to the ranks of the technologically advanced started as recently as 1990s, and, although having had some success, the country's digital resources remain grossly inadequate to support the growing public demand for information and education. Despite its state of retardation, the problems of preserving digital sources in Russia are evident to concerned specialists in the fields of informational science and archive work. Although these and other related problems are not addressed widely enough, they have gradually surfaced as an undeniable priority for the international preservation community. There is a promise to continue the necessary training and education that will link the national Russian library system with more collaborative projects and with leading international organizations. © 2004, Emerald Group Publishing Limited. All rights reserved.
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00246 tex.type: [object Object]
Keywords: Digital storage; Libraries; Russia; dept.ils

Managing the information revolution: library management, the control of prescriptive technologies, and the future of librarianship - Sierpe, Eino (Library Management, 2004)
This article seeks to promote a critical perspective on the present conceptualization of library management and the problems posed by technology. More specifically, it addresses the challenges faced by library administrators in relation to computing technologies. Through the adoption of Ursula Franklin's view of technology as “practice”, the article contrasts the practice of holistic and prescriptive technologies in library contexts. It also addresses the transformations of librarianship and the increasing adoption of prescriptive technological models. To exemplify the ongoing destruction of traditional librarianship, the three practices that comprise the fundamentals of librarianship are analyzed, namely, cataloging, collection development, and reference work. © 2004, Emerald Group Publishing Limited
3 citations (Crossref) [2023-10-31] Citation Key Alias: pop00170 tex.type: [object Object]
Keywords: Information management; Librarianship; Libraries; dept.ils

Best practices, standards and techniques for digitizing library materials: a snapshot of library digitization practices in the USA - Liu, Yan Quan (Online Information Review, 2004)
This study investigates current practice in digitizing library materials in the USA. Building a good digital collection has been a common task, pervasive in all types of libraries. Digitization becomes more and more crucial, affecting libraries while they work towards becoming digital. Researchers and practitioners would like to know what practices have been developed to deal with the challenges that pose the most significant problems or concerns for libraries in digitization. Through probing some widespread issues on what materials to digitize, and the associated standards and technologies in digitization in US libraries, this survey of current literature reveals a number of prominent library digitization practices, methods and challenges, and highlights the best practices, trends and interests in library digitization pertaining to both policy and technology marketplace issues.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/059-597-493-339-542 tex.type: [object Object]
Keywords: Analog to digital conversion; Data processing; Digital libraries; Document image processing; Electronic media; Information and Library Science; Multimedia systems; Project management; Public policy; Societies and institutions; Standards; Technical problems; United States of America; dept.ils

Is the education on digital libraries adequate - Liu, Yan Quan (New Library World, 2004)
This study investigates the state of education for digital libraries. For this study, a Web survey was conducted of syllabi of courses on the subject of digital libraries (DL). Similarities and differences on such subjects as teaching emphases, course outlines, textbooks and assignments were compared. The majority of classes now contain a “hands-on” element, a practical component of the course that requires that the students interact with digital libraries. Not all of the course contents are up-to-date in the field of library and information technology. While the quality of DL education seems to have advanced at those schools and institutions that offer classes with “hands-on” requirements, the educational approach at many of the “hands-off” universities seems somewhat technophobic and overly dependent on outdated pedagogical methods. Those students who have received practical experience with digital libraries, like those provided in the “hands-on” courses, appear to be best served for future practice in the field of librarianship. © 2004, Emerald Group Publishing Limited
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-352-432-311-492 tex.type: [object Object]
Keywords: Digital libraries; Europe; Libararies; Library facilities; North America; Surveys; dept.ils

Preparation, microstructure and physical characteristics of ferroelectric pb 5 ge 3 O 11 thin films for memory application - Liu, Y. X.; Caragianis-Broadbridge, Christine; Lehman, A. H.; McGuinness, J. K.; Ma, Tso-Ping (MRS Proceedings, 2003)
We report sol-gel process of Pb5Ge3O11 (PGO) as well as the microstructure and physical properties of ferroelectric PGO films for memory applications. The PGO sol was prepared from lead acetate hydrate, germanium isopropoxide, and di(ethylene glycol) ethyl ether. The reactions taking place during the sol-gel process were examined in detail, Diethanolamine (DEA) was added to help maintain the desired species ratio and prevent germanium oxide precipitation. The preferred orientation of the PGO thin films was well controlled by the heating and reflux procedures in the sol-gel preparation process. Additionally, to examine the impact of post-deposition processing, selected samples were oxygen annealed at temperatures ranging from 450-650°C. The samples were characterized with X-ray diffraction (XRD), non-contact (planview) atomic force microscopy (NC-AFM). The resulting data indicate that the microstructure and physical properties of PGO films depend strongly on the precursor preparation as well as the post deposition annealing temperature.
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00135 tex.type: [object Object]
Keywords: Atomic force microscopy; Ferroelectric materials; Glove boxes; Isopropoxide; Lead compounds; Low-power memory; MISFET devices; Microstructure; Sol-gels; Thermal effects; Thin films; X ray diffraction; dept.ils

Where does professional education on digital libraries lead our new librarians - Liu, Yan Quan (International Conference on Asian Digital Libraries, 2003)
This study investigates the state of school education for digital libraries. For this study, a web survey was conducted of syllabi of courses on the subject of digital libraries. Similarities and differences on such subjects as teaching emphases, course outlines, textbooks and assignments were compared. The majority of classes now contain a "hands-on" element, a practical component of the course that requires that the students interact with digital libraries. Those students who have received practical experience with digital libraries, like those provided in the "hands-on" courses, are best served for future practice in the field of librarianship. © Springer-Verlag Berlin Heidelberg 2003.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Digital libraries; E-learning; Education; Practical experience; Professional education; School education; Students; Teaching; Web surveys; dept.ils

Transformations of Librarianship in Support of Learning Communities - Sierpe, E.; De la Peña McCook, K. (Reference and User Services Quarterly, 2003)
Keywords: dept.ils; ⛔ No DOI found

The use of statistics in the managerial process by public library directors in China and the USA: a cross‐country survey - Liu, Yan Quan (Library Management, 2001)
Librarians have been involved in collecting and disseminating statistics for many years. Utilising statistics to describe and assess the operation of library activities as a part of library tradition has received growing attention from researchers, policymakers, library managers, and professionals. However, few studies have investigated how statistics are used in libraries. This report compares directors’ uses of statistics provided by national agencies in the USA and China to highlight the differences and similarities between the ways in which the two groups of directors make use of statistics, and the statistical information that directors find particularly useful. The results are intended to provide library administrators with an insight of how library statistics are used in the managerial process, and may also help the national statistical providers to obtain an understanding of the characteristics and pattern of use of their products. © 2001, MCB UP Limited
3 citations (Crossref) [2023-10-31] Citation Key Alias: pop00177 tex.type: [object Object]
Keywords: China; Libraries; Management; Public Libraries; Statistics; USA; dept.ils

The transition from paper to electronic journals: Key factors that affect scholars' acceptance of electronic journals - Kim, Hak Joon (Serials Librarian, 2001)
The primary purpose of this paper is to investigate what factors crucially affect scholar's acceptance of e-journals. Before reviewing various aspects of e-journals, it is necessary to fully understand the traditional journal system, because the developments, roles, and deficiencies of the paper journal system will illustrate some basic requirements for successful e-journals. This article also examines the developments of e-journals and presents a comprehensive examination of the economic, technological and cognitive, and sociological aspects of e-journals based upon an extensive literature review. With regard to the economic and technological and cognitive aspects, the benefits of scholarly e-journal publishing appear to be, by and large, favorable to the transition from paper to electronic journals. However, the major stumbling block is the credibility of scholarly e-journals. Whether or not scholars can obtain the same recognition or rewards through e-journal publication as they obtain through paper journal publication must be one of the key factors that affect scholar's acceptance of e-journals.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-081-770-161-36X tex.type: [object Object]
Keywords: Electronic journals; Journal functions; Journal system; Scholarly communication; Scientific reward system; dept.ils

A comparison of public library use of statistics – a cross‐country survey report - Liu, Yan Quan (New Library World, 2001)
Librarians have been involved in collecting and disseminating statistics for many years. Utilizing statistics to describe and assess the operation of library activities as a part of library tradition has received growing attention from researchers, policymakers, library managers, and professionals. However, few studies have investigated how statistics are used in libraries. This report compares directors’ uses of statistics provided by national agencies in the USA and China to highlight differences and similarities of the uses the two countries’ directors make of statistics and the statistical information that directors find particular useful. The results are intended to provide library administrators with an insight of how library statistics are used in the managerial process and may also help the national statistical providers to obtain an understanding of the characteristics and pattern of use of their products. © 2001, MCB UP Limited
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/154-713-030-974-661 tex.type: [object Object]
Keywords: China; Librarians; Libraries; Management; Statistics; USA; dept.ils

A dynamic model of museum and academic library cooperation - Reilly, Karen E; Verges, Jolene De (College & Undergraduate Libraries, 2001)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/187-608-446-797-462 tex.type: [object Object]
Keywords: dept.ils

Development of a web-based faculty publications database - Bai, S.; Kelly, P. (Bulletin of the Medical Library Association, 2000)
Keywords: Connecticut; Databases; Bibliographic; Faculty; Medical; Internet; Libraries; Medical; Publications; Universities; article; data base; dept.ils; education program; information system; library; publication; research; ⛔ No DOI found

Personalizing information retrieval using task features, topic knowledge, and task product - Liu, Jingjing (International ACM SIGIR Conference on Research and Development in Information Retrieval, 2009)
3 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: dept.ils

The impact of digital resource and service use on urban residents in new england public Libraries—A survey report - Liu, Yan Quan; Wnuk, Agnes (Public Library Quarterly, 2009)
Today, access to digital information is essential to patrons using public libraries, whether they have contact with computers at home, work or school or whether the public library is their only contact. In order to evaluate and ultimately enhance public library digital resources and services, it is critical for administrators, librarians and digital information architects to recognize the impact their current digital offerings have on users. This study utilizes a survey to gauge the perceptions of patrons who use digital resources and services in six urban New England public libraries as part of ongoing research into digital information access in public libraries in the United States from the perspective of users.
3 citations (Crossref) [2023-10-31] tex.ids: lens.org/052-608-977-611-377 tex.type: [object Object]
Keywords: Digital divide; Digital libraries; Digital resources; Digital resources services; New England public libraries; Public libraries; Urban libraries; dept.ils; peer-reviewed

Exploiting the social style of patrons to improve their satisfaction with the reference interview - Sisselman, Peggy (Library Review, 2009)
Purpose: The purpose of this paper is to discover whether the social styles of patrons affects their perception (and librarians' perception) of the quality of the reference interview. Also, whether learning to assess social styles of patrons improves perception of the quality of the reference interview. Design/methodology/approach: The researcher observed 24 reference interviews, assessed the social style of each patron using a checklist of behavioral characteristics; both patrons and librarians confidentially filled out a survey to assess the outcome of the reference interview. Findings: It appears that the social style of patrons has some effect on how both librarians and patrons perceive the outcome of the reference interview. There also appears to be a correlation between the librarians' awareness of the social styles of people and the outcome of the reference interview. Practical implications: Literature has not provided any data on how social style theory on the four social styles (analytical, expressive, driver, amiable) could be used to improve the reference interview. Originality/value: Social style theory has been explored in academic settings and in the areas of marketing and sales, but not yet in public libraries. © Emerald Group Publishing Limited.
4 citations (Crossref) [2023-10-31] tex.ids: lens.org/128-369-272-495-02X tex.type: [object Object]
Keywords: Customer satisfaction; Individual perception; Interpersonal communications; Reference services; Social dynamics; dept.ils

Enhancing digital information access in public libraries - Ayers, Kathleen; Liu, Yan Quan (Proceedings of The Asist Annual Meeting, 2007)
Purpose To explore the impact of public digital library resources on urban residents, to elucidate the current usage patterns of public digital library resources/services and levels of satisfaction with the resources/content in urban digital libraries and make recommendations as to steps that would improve service to this population. Design/Methodology/Approach We conducted an anonymous user-completed survey study of 6 urban libraries to collect demographic and information regarding satisfaction with Digital Library (DL) resource and patterns of use. Findings Our respondents represented a cross section of races, genders, ages, and educational backgrounds. Our results in this much-needed area of study demonstrate that libraries should plan to provide more access, less filtering, regular upgrades, and more training to use the resources. Practical Limitations/Implications Larger studies should be used to follow up this report, in order to be able to obtain a generalized understanding of overall patterns of urban residents using DLs in public settings. Recruitment techniques did not adequately sample potential (but not current) DL users. Originality/Value This study contributes to a scant empirical data set addressing the impact that access to public digital information and services have on urban residents. We offer new data and recommendations that will guide public library administrators in enhancing the impact, efficiency and value of public DL resources/services to improve the digital learning environment for life-long educaiton at all levels in a broad community of urban users.
0 citations (Crossref) [2023-10-31] tex.ids: lens.org/027-715-068-622-316 tex.type: [object Object]
Keywords: dept.ils; ⛔ No DOI found

Developing an integrated public library service in Dongguan, one of China's fastest growing cities - Liu, Yan Quan; Li, Donglai (New Library World, 2007)
Purpose - The purpose of this case study is to explore the construction pattern and issues involved in the development of an urban library service system in China. Design/methodology/approach - This study was conducted through an analytical evaluation of the development of an integrated public service system and its distribution of information among libraries and information centers in an urban community. Findings - Constructing an integrated public service system is an important trend in urban libraries in the new millennium. Drawing from the Dongguan library's integrated public service system that aims to master better various resources from whole service area, this text summarizes technology innovation and the significant results of the Dongguan library system redevelopment, providing an absorbing insight into developments in the Chinese public library service. Originality/value - While the ultimate goal of integration is to provide better services to meet the information-seeking needs of urban residents, it is necessary to meet these needs through a technological breakthrough in the administration of clustered libraries, to instill a central branch system, and to work out the advantages of group service.
0 citations (Crossref) [2023-10-31] tex.ids: lens.org/074-087-094-612-648 tex.type: [object Object]
Keywords: China; Digital libraries; Library management Public sector organizations; Public libraries; dept.ils

Digital information access in urban/suburban communities: A survey report of public digital library use by the residents in Connecticut - Liu, Yan Quan; Martin, Craig; Roehl, Eileen; Yi, Zhixian; Ward, Sheila (OCLC Systems and Services, 2006)
Purpose - The purpose of this paper is to explore the impact of public digital services on urban/suburban residents, to uncover the current usage of public digital services and levels of satisfaction with the digital resources/content in urban digital libraries (networked computers with specific information infrastructure designed free for public use). Design/methodology/approach - A qualitative approach is used as a main stream in the research framework as the method of inquiry. Qualitative one-to-one interviews include surveying users who use public library websites, observing the users, consulting librarians about the users, and interviewing the users. Findings - Provides demographic patterns of the patron's interaction with the digital services public libraries provide, and the satisfaction and compliances the residents have regarding information access through the digital technology in urban/suburban Connecticut. Practical implications - Because of the small number of participants, this study has limitations in being generalized to an understanding of overall patterns of urban residents using digital resources in public settings in the USA or elsewhere, however, it could be a good pilot study for a nation-wide survey with the methods tested. Originality/value - This study helps fulfill the scant empirical attention given to the impact access to public digital information or use of digital library services on the urban/suburban residents, offers new data that help public library administrators enhance the impact, efficiency and value of the public digital library services to improve the digital learning environments for life-long education at all levels in a broad community of urban-suburban users. © Emerald Group Publishing Limited.
5 citations (Crossref) [2023-10-31] tex.ids: lens.org/051-401-327-795-077 tex.type: [object Object]
Keywords: Design/methodology/approach; Digital learning environment; Digital libraries; Digital technologies; Information retrieval; Information services; Information studies; Life-long educations; Public libraries; Public library; Qualitative approach; Specific information; Surveys; dept.ils

The Enlightenment of Pew Research Center's Information Management Practice on Academic Library Think Tank Services / 皮尤研究中心信息管理实践对学术图书馆智库服务的启示 - Liang, X.; Liu, Yan Quan (Library & Information, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Investigation and Research on the Application of Artificial Intelligence Technology in Library Service / 图书馆服务中人工智能技术应用的调查研究 - Yang, Z.; Wang, Y.; Liu, Yan Quan; Qu, Z. (Library/TU Shu Guan, 2019)
Keywords: dept.ils; ⛔ No DOI found

Behind the transmitter: differences in archival practices between nonprofit and commercial radio stations - Falcone, Michael; Real, B.; Liu, Y. Q. (Journal of Archival Organization, 2020)
Many radio collections within the United States are maintained in more informal program libraries and archives in hundreds of geographically dispersed broadcasting stations throughout the country. To assess the full extent of this problem and real risk posed to station-owned radio collections, this article assesses the results of a survey administered across twenty-seven nonprofit and commercial stations or corporate parent companies. Nonprofit stations, its findings suggest, are more likely to actively maintain their archives and do so in a manner that shows awareness of current archival standards, whereas commercial stations are less likely to exert active stewardship over their collections. © 2020 The Author(s). Published with license by Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31] tex.ids: falconeTransmitterDifferencesArchival2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086264842 type: Article
Keywords: Radio; audio preservation; college radio; dept.ils; peer-reviewed; radio archives; radio preservation

The provision of patron services in Chinese academic libraries responding to the COVID-19 pandemic - Guo, Yajun; Yang, Zinan; Yang, Zhishun; Liu, Yan Quan; Bielefield, Arlene; Tharp, Gregory (Library Hi Tech, 2020)
Purpose: The purpose of this paper is to identify the measures employed in the provision of patron services in Chinese academic libraries responding to the COVID-19 pandemic, noting the challenges and issues inherent in providing substantial services while undergoing a public health emergency. Design/methodology/approach: This paper uses an analytical survey study of 137 Chinese academic libraries using data collected through a combination of website investigation, social media access and direct correspondences. Findings: Over 94% of Chinese academic libraries released COVID-19-related information through their websites; the majority switched their service focus to partly or solely remotely online, including remote access, free electronic resources, virtual references reachable 24/7 and research support services deliverable online; services of print materials were altered to e-books for conveniences. Research limitations/implications: It should be noted that the survey was conducted from February 12 to April 5, 2020; because of the rapid updates to the library's website and social media channels, the status of their patron services are in the process of dynamic changes and that there should be many libraries that have adopted some patron service methods, but this study is difficult to cover comprehensively. In addition, patron services carried out offline by the surveyed libraries but not disclosed on the online platform could not be analyzed in a way that would be consistent with the data provided by the survey. Originality/value: By providing evidence of the current status of patron services in Chinese academic libraries during the COVID-19 pandemic, this study helps fulfill the scant empirical attention given to the impact of nationwide public health crises on academic libraries and offers new data of the best practices that help library administrators enhance the impact, efficiency and value of library services to their target community users. © 2020, Emerald Publishing Limited.
32 citations (Crossref) [2023-10-31] tex.ids: guoProvisionPatronServices2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85088570958 type: Article
Keywords: Academic libraries; COVID-19; China; Patron services; Survey; Virtual services; dept.ils; peer-reviewed

Information Accessibility, How Far Is It?——An Empirical Research of 146 US Urban Public Libraries / 信息无障碍,距离还有多远?——对146家美国城市公共图书馆的调查 - Guo, Y.; Xi, J.; Liu, Yan Quan (图书馆论坛 [Sun Yat-Sen Library of Guangdong Province], 2020)
文章以美国城市公共图书馆协会146家图书馆为调查对象,借助无障碍评估工具WAVE对这些馆网站主页进行测评,逐一开展网站访查和内容分析,统计为残障用户提供服务的情况。调查发现,美国城市公共图书馆网站达到Section 508信息无障碍标准的比例只有15%,“缺少表单标签”“链接图像缺少替代文本”等是常现错误;55%图书馆网站主页有残障用户服务信息。我国公共图书馆应重视信息无障碍建设,遵循信息无障碍标准,定期进行审查与维护,借助信息无障碍技术提供残障服务。
Keywords: dept.ils; ⛔ No DOI found; 信息无障碍; 公共图书馆; 残障用户; 美国; 调查

Are Ivy League libraries’ websites ADA compliant? - Yang, Wenfan; Zhao, Bin; Liu, Yan Quan; Bielefield, Arlene (Information Technology and Libraries, 2020)
As a doorway for users seeking information, library websites should be accessible to all, including those who are visually or physically impaired and those with reading or learning disabilities. In conjunction with an earlier study, this paper presents a comparative evaluation of Ivy League university library homepages with regard to the Americans with Disabilities Act (ADA) mandates. Data results from WAVE and AChecker evaluations indicate that although the error of Missing Form Labels still occurs in these websites, other known accessibility errors and issues have been significantly improved from five years ago.
3 citations (Crossref) [2023-10-31]
Keywords: dept.ils; peer-reviewed

Impact of Subjective Norms on Assertive Impression Management Motivation/ 主观规范对获得型I印象管埋动机的影响机制研究 - Zhao, Bin; Han, Y.; Liu, Yan Quan (Software Science, 2020)
Keywords: dept.ils; ⛔ No DOI found

A complete assessment of tagging quality: A consolidated methodology - Choi, Yunseon (Association for Information Science and Technology, 2015)
This paper presents a methodological discussion of a study of tagging quality in subject indexing. The data analysis in the study was divided into 3 phases: analysis of indexing consistency, analysis of tagging effectiveness, and analysis of the semantic values of tags. To analyze indexing consistency, this study employed the vector space model-based indexing consistency measures. An analysis of tagging effectiveness with tagging exhaustivity and tag specificity was conducted to ameliorate the drawbacks of consistency analysis based on only the quantitative measures of vocabulary matching. To further investigate the semantic values of tags at various levels of specificity, a latent semantic analysis (LSA) was conducted. To test statistical significance for the relation between tag specificity and semantic quality, correlation analysis was conducted. This research demonstrates the potential of tags for web document indexing with a complete assessment of tagging quality and provides a basis for further study of the strengths and limitations of tagging.
3 citations (Crossref) [2023-10-31] tex.type: Proceedings paper Citation Key Alias: ISI:000351395800010
Keywords: Consistency analysis; Consistency measures; Correlation analysis; Indexing (of information); Information retrieval; Latent Semantic Analysis; Organization of informations; Quality control; Quantitative measures; Semantics; Statistical significance; Subject indexing; Vector spaces; clinical trial; correlation analysis; data analysis; dept.ils; human; information retrieval; linguistics; model; organization of information; quantitative study; statistical significance; subject indexing

Analyzing tagging patterns by integrating visual analytics with the inferential test - Choi, Yunseon (ACM/IEEE Joint Conference on Digital Libraries, 2015)
Due to the large volume and complexity of data, exploring data using visual analytics has become more helpful to interpret and analyze it. The box plot is one of graphical ways and is the most common technique for presenting and summarizing statistics. In this paper, we focus on discussing the tagging patterns by integrating visualization assessment using the box plot with the Shapiro-Wilk test. © 2015 Author.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Data analytics; Data visualization; Digital libraries; Large volumes; Shapiro-Wilk tests; Social tagging; Visual analytics; Visualization; data analytics; data visualization; dept.ils; social tagging

Content analysis of social tags generated by health consumers - Joo, Soohyung; Choi, Yunseon (ACM/IEEE Joint Conference on Digital Libraries, 2015)
This poster presents preliminary findings of user tag analysis in the domain of consumer health information. To obtain user terms, 36,205 tags from 38 consumer health information sites were collected from delicious.com. Content analysis was applied to identify the dimensions and types of the collected tags. The preliminary findings showed that user generated tags covers a variety of aspects of health information, ranging from general terms, subject terms, knowledge type, and to audience. General terms and subject terms were observed dominantly by showing 31.7% and 22.8% respectively. © 2015 Authors.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Consumer health information; Content analysis; Digital libraries; Health; Health informations; Knowledge types; Qualitative analysis; Social Tags; Social networking (online); Social tagging; User-generated; consumer health information; dept.ils; qualitative analysis; social tagging

Effective techniques for the promotion of library services and resources - Yi, Zhixian (Information Research-an International Electronic Journal, 2016)
Introduction. This study examines how Australian academic librarians perceive techniques for promoting services and resources, and the factors affecting the perceptions regarding effectiveness of techniques used. Method. Data were collected from an online survey that was sent to 400 academic librarians in thirty-seven Australian universities. The response rate was 57.5%. Analysis. The qualitative data were analysed using content analysis. The collected quantitative and qualitative data were analysed using descriptive and inferential statistics (ordinal regressions). Results. Librarians used a variety of techniques to promote services and resources. Demographic variables, human capital variables and library variables were significant predictors of perceptions of the effective promotion techniques used. However, this study indicates that other independent variables such as number of different library professional positions and years involved in all library services made no difference. Conclusions. This study provides a better understanding of academic librarians' attitudes and views towards techniques for promoting services and resources. Librarians may use the results to reflect on the effectiveness of these techniques, to balance the weight of the factors' influences and to better understand various promotion techniques. This will enable them to promote library services and resources more effectively in the future.
tex.article-number: 702 tex.unique-id: ISI:000386350500011
Keywords: dept.ils; ⛔ No DOI found

Current market demand for core competencies of librarianship-a text mining study of american library association's advertisements from 2009 through 2014 - Yang, Qinghong; Zhang, Xingzhi; Du, Xiaoping; Bielefield, Arlene; Liu, Yan Quan (Applied Sciences-Basel, 2016)
As librarianship evolves, it is important to examine the changes that have taken place in professional requirements. To provide an understanding of the current market demand for core competencies of librarianship, this article conducts a semi-automatic methodology to analyze job advertisements (ads) posted on the American Library Association (ALA) Joblist from 2009 through 2014. There is evidence that the ability to solve unexpected complex problems and to provide superior customer service gained increasing importance for librarians during those years. The authors contend that the findings in this report question the status quo of core competencies of librarianship in the US job market.
23 citations (Crossref) [2023-10-31] tex.article-number: 48 tex.unique-id: ISI:000371827200001
Keywords: Competency; Job advertisement; Librarianship; Text mining; dept.ils; peer-reviewed

A library in the palm of your hand: mobile services in top 100 university libraries - Liu, Yan Quan; Briggs, Sarah (Information Technology and Libraries, 2015)
What is the current state of mobile services among academic libraries of the country's top 100 universities, and what are the best practices for librarians implementing mobile services at the university level? Through in-depth website visits and survey questionnaires, the authors studied each of the top 100 universities' libraries' experiences with mobile services. Results showed that all of these libraries offered at least one mobile service, and the majority offered multiple services. The most common mobile services offered were mobile sites, text messaging services, e-books, and mobile access to databases and the catalog. In addition, chat/IM services, social media accounts and apps were very popular. Survey responses also indicated a trend towards responsive design for websites so that patrons can access the library's full site on any mobile device. Respondents recommend that libraries considering offering mobile services begin as soon as possible as patron demand for these services is expected to increase.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/012-328-507-257-353 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.ils; peer-reviewed

Web 2.0 applications' usage and trends in top US academic libraries - Boateng, Frank; Liu, Yan Quan (Library Hi Tech, 2014)
Purpose - This paper aims to explore Web 2.0 technologies usage and trends in the top 100 US academic libraries as exemplified through the academic library websites. Design/methodology/approach - The top 100 universities were selected from the US News & World Report's (USNWR) 2013 ranked list's top 100 of the best colleges in the USA. Content analysis was used in terms of quantitative approach. A checklist was developed as the main research instrument based on other checklists and questionnaires. Each of the selected university library websites was visited within a period of two weeks to explore implementation and usage of web tools, including SNS, blog, RSS, wikis, podcast/vodcast, and social bookmarking/tagging. Findings - All 100 academic libraries had a social media presence on Facebook and Twitter, making SNS the most widely applied Web 2.0 tool. The wild was the least applied Web 2.0 technology, with a 34 percent participation rate. Blog was the second most popular tool with a 99 percent participation rate, followed by RSS and IM/Chat with 97 percent and 91 percent respectively. The vodcast and podcast had 47 percent and 46 percent participation rates respectively, while social bookmarking/tagging were also used by 39 percent of the academic libraries. Research limitations/implications - This study is completely based on publicly available data regarding usage of Web 2.0 applications. Web 2.0 tools used on library intranets were not analyzed for this study. Outcomes suggest that academic libraries are increasingly using Web 2.0 applications to promote themselves, enhance library services, and highlight resources to patrons. Originality/value - This is the first research that draws an overall picture of the usage and trends of Web 2.0 applications in the top 100 US academic libraries. This study demonstrates some noticeable patterns regarding usage, trends, and adoption which are relevant to how Web 2.0 applications are perceived and used within academic libraries. The study provides academic libraries with helpful information to better meet their user needs by effectively applying Web 2.0. Additionally, library managers, librarians and other libraries may also find this research beneficial as they plan to deploy Web 2.0.
54 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-270-484-139-930 tex.unique-id: [object Object]
Keywords: Academic libraries; Library services; Technology usage; Web 2.0; dept.ils; peer-reviewed

From siloed data to linked data: Developing a social metadata repository - Choi, Yunseon (Proceedings of the American Society for Information Science and Technology, 2014)
Although social data has been investigated and discussed regarding its impact on indexing and retrieval performance on the web, there has been little research conducted on storing or linking social data and identifying bibliographic relationships among social data for further use of social data. In this paper, we discuss our work in progress that aims to develop a social metadata repository which would be an important implication for making social data more valuable and reusable for searching and retrieval. We describe FRBR (Functional Requirements of Bibliographic Records) conceptual model's Entity-Relationship (ER) view on bibliographic relationships and demonstrate how social metadata are encoded in RDA (Resource Description and Access) and how the implicit bibliographic relationships of social data are explicitly represented as RDF (Resource Description Framework) triples (Subject - Predicates - Objects) with links to external sources. We believe that the shareable and linked metadata repository of social data is remarkably significant, not only because it supports the accessibility to related documents, but also because it is clarifying the implicit semantic relationships among social data.
0 citations (Crossref) [2023-10-31]
Keywords: FRBR; Linked Data; Metadata; RDA; RDF; Social data; Social tags; dept.ils

The impact of senior citizens' use of online social networks on their cognitive function - Kim, Hak Joon; Kim, Joan (International Journal of Research Studies in Educational Technology, 2014)
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/044-406-155-069-878
Keywords: dept.ils

Reading from an LCD monitor versus paper: Teenagers’ reading performance - Kim, Hak Joon; Kim, Joan (International Journal of Research Studies in Educational Technology, 2013)
25 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/067-587-714-739-234
Keywords: dept.ils

Using dwell time as an implicit measure of usefulness in different task types - Liu, Chang; Liu, Jingjing; Belkin, Nicholas J; Cole, Michael J; Gwizdka, Jacek (Proceedings of the American Society for Information Science and Technology, 2011)
In this study, we attempted to use dwell time on content pages as a predictor of document usefulness, and evaluated the prediction performance in different types of tasks. A user study was conducted to address this research problem. A total of 32 participants conducted searches associated with 4 different tasks, varying along several task type dimensions. In the study, participants were asked to save documents that were useful for the tasks during the searches. Participants' information-seeking activities were recorded. Using the logged dataset, we used the recursive partitioning method to identify the best threshold (cutoff point) of dwell time to predict which pages would be useful, i.e., be saved by the users. We examined the differences in the threshold and compared the prediction performance for each type of task. Our results indicate that the threshold should be developed according to the type of task users are working on. While the prediction performance using dwell time as the only indicator of document usefulness is acceptable for Factual tasks, it is not good for Intellectual tasks. Our results have implications on IR system design.
5 citations (Crossref) [2023-10-31]
Keywords: Dwell time; Personalization; Task type; Usefulness prediction; dept.ils

Search task difficulty: the expected vs. the reflected - Liu, Jingjing; Belkin, Nicholas J (International ACM SIGIR Conference on Research and Development in Information Retrieval, 2011)
We report findings on how the user's perception of task difficulty changes before and after searching for information to solve tasks. We found that while in one type of task, the dependent task, this did not change, in another, the parallel task, it did. The findings have implications on designing systems that can provide assistance to users with their search and task solving strategies.
1 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Dependent tasks; Designing systems; Predicted difficulty; Reflected difficulty; Searching for informations; Task difficulty; Task type; User's perceptions; dept.ils

Understanding searchers' perception of task difficulty: Relationships with task type - Liu, Jingjing; Liu, Chang; Yuan, Xiaojun; Belkin, Nicholas J (Proceedings of the American Society for Information Science and Technology, 2011)
We report findings that help us better understand the difficulty of tasks which involve information seeking, retrieving, gathering, and use. We examined the data gathered from two interactive information retrieval user studies on how users' perception of task difficulty changes before and after searching for information to solve tasks, and how the difficulty of tasks relates with users' background, previous experience with the tasks, and knowledge of the task topics, etc. The two studies employed carefully designed tasks with different types along several dimensions: task structure (subtasks being dependent upon or parallel with each other), task goal in quality (being specific or amorphous), and naming (being named or unnamed). It was found that while in some types of tasks, users' perceptions of task difficulty did not change before and after working on the tasks, in others, this did, either increasing or decreasing. Specifically, in the dependent-structured task, this did not change. In the parallel-structured or specific/named task, it decreased. In the amorphous/unnamed task, it increased. We also found that users' background factors do not normally correlate with their perceived task difficulty, or perceived difficulty change. In addition to helping understand the dynamic and complex nature of task difficulty, our findings have implications for system design that can provide assistance to users with their search and task solving strategies.
6 citations (Crossref) [2023-10-31]
Keywords: Expected difficulty; Reflected difficulty; Task difficulty; Task type; dept.ils

Web 2.0 applications in top Chinese university libraries - Han, Zhiping; Liu, Yan Quan (Library Hi Tech, 2010)
Purpose - This paper aims to explore the status and construction pattern of Web 2.0 technologies employed in top Chinese university libraries, their functionalities and features. Design/methodology/approach - A combination of online survey and content analysis methodology is applied to a sample of 38 top Chinese university libraries' web sites. The Web 2.0 tools are categorized by generally accepted standards with some adjustment for library practices. Data were collected by accessing these university library web sites on two separate occasions during the period of February 10-20, 2009 by utilizing a checklist of 52 questions. Findings - More than two-thirds of the 38 top Chinese university libraries apply one or more kinds of Web 2.0 tools through the basic functions of their web sites. Among six types of tools, Catalog 2.0 and RSS are the most common, while IM, Blog, SNS and Wiki are less frequent. Research limitations/implications - Internal applications that are not publicly accessible contain hidden information that may not be gathered through content analysis since these links usually cannot be found on library web sites. It is difficult to get exact information as to the applications of Web 2.0 in these libraries without an interview method in combination to observation. Originality/value - This study provides an overall picture of Web 2.0 tools developed in top Chinese university libraries, allowing for future evaluation and planning. The implementation of Web 2.0 applications and their constructing pattern is not only indicative of the development of the Chinese digital libraries, but also to their development of digital libraries in the world at large.
48 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/148-213-665-014-156 tex.unique-id: [object Object]
Keywords: China; Digital libraries; University libraries; Worldwide web; dept.ils; peer-reviewed

The use of national public library statistics by public library directors - Liu, Yan Quan; Zweizig, Douglas L (The Library Quarterly, 2001)
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-574-806-615-498 tex.type: [object Object]
Keywords: dept.ils; ⛔ No DOI found

Technical service outreach strategies for academic libraries - Toce, Jacqueline; Schofield, Cindy (Technical Services Quarterly, 2011)
The model of a library staff divided into technical and informational service divisions remains common-especially among academic libraries. The authors argue that in many ways it is now the technical services division that is best positioned to provide outreach services to a community-whether at the university or municipal level. Maintaining bibliographic access amid the changing information landscape hinges on a clear understanding of systems, metadata, and traditional organizational skills, all home grown in the back rooms of conventional libraries. The authors cite examples of library outreach that emanated from technical service departments and conclude that the sequestered staffs of the past must make themselves indispensible today by sharing their knowledge and talents, offering services to their communities that require their technical expertise, and advance the mission of the library organization. © Taylor & Francis Group, LLC.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/135-473-790-983-166 tex.type: [object Object]
Keywords: Academic libraries; Catalogers; Cooperative; Outreach; Service; Southern connecticut state university; Technical services; dept.ils; dept.lib

Private life, public diplomacy: Tibor Hirsch and documentary filmmaking for the cold war USIA - Real, Brian (Historical Journal of Film, Radio and Television, 2020)
The United States Information Agency acted as a significant patron of American independent and nontheatrical filmmakers during the 1960s, commissioning short documentaries to carry positive messages about America to foreign audiences. While much of the existing scholarship on the USIA’s motion picture output focuses on works that address major policy issues such as the civil rights movement or that were made by directors who went on to have well-known careers, many of its films and directors have been forgotten. One such filmmaker is Tibor Hirsch, whose past as a refugee from the 1956 Hungarian Revolution influenced his films Transportation USA (1966) and Six Who Fled (1972). Hirsch’s earlier career as a photojournalist informed his work for the USIA, while the style he developed through making government films led directly into his later career as a highly successful television commercial director.
0 citations (Crossref) [2023-10-31] tex.ids: realPrivateLifePublic2019, realPrivateLifePublic2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85073924504 type: Article
Keywords: dept.ils; peer-reviewed

Public Libraries and the Opioid Crisis, Part 1: Context and Commitment - Real, Brian; Bogel, Gayle (Public Library Quarterly, 2019)
Public libraries have been significantly affected by the opioid crisis. The fact that patrons can enter libraries freely and do not need a reason to be there has resulted in overdoses occurring in many such buildings throughout the country. In response to this, library directors have developed plans of action that, in some cases, include training librarians to administer the opioid overdose reversal drug Naloxone. This present article – the first in a two-part study – is based on interviews with representatives from libraries that have been significantly affected by the opioid crisis. After describing these community circumstances, the authors analyze various ways that each library has prepared to respond to overdoses and other emergency situations.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/172-972-683-218-803, pop00020 tex.type: [object Object]
Keywords: Narcan; Public libraries; dept.ils; opioid dependency; opioids; peer-reviewed

Public Libraries and the Opioid Crisis, Part 2: Community-Centered Responses - Real, Brian; Bogel, Gayle (Public Library Quarterly, 2019)
Numerous articles from major national newspapers have covered the fact that as the opioid crisis has become a pervasive problem in the United States, overdoses in public libraries have become a somewhat common occurrence. Many of these discussions center on librarians being trained to use the overdose reversal drug Naloxone, and that was the primary focus of the first part of this two-part study. However, this second article discusses what libraries are doing to mitigate the impacts of the crisis and help persons from vulnerable populations before matters escalate to become emergency situations. The authors document how libraries are attempting to educate their communities about the opioid crisis, ways they have partnered with community organizations to help opioid dependent persons, and how they have addressed various facilities and security concerns for their buildings.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/040-002-193-003-128, pop00139 tex.type: [object Object]
Keywords: Public libraries; dept.ils; facilities management; opioids; peer-reviewed; security; vulnerable populations

Confronting librarianship and its function in the structure of white supremacy and the ethno state - Sierpe, Eino (Journal of Radical Librarianship, 2019)
Rising socio-cultural and political tensions have helped increase awareness about long-standing structures of violence and abuse, as we have seen in the development and tumultuous expansion of the #MeToo movement. However, other significant conditions of injustice and oppression continue without drawing attention. This seems to be the case with the library profession. Despite strong and persistent links to white supremacy and a well-established record excluding minorities from its ranks, the library profession has been remarkably successful in nurturing an unassailable public image of virtuous liberal benevolence and near mythical devotion to the highest ideals of freedom, individual rights, and democracy. Its unsurpassed ability in evading scrutiny or criticism of any serious consequence while maintaining a strong record of dedicated service to white power is all the more remarkable at a time where social media is used to amplify campaigns against injustices or organizations believed responsible for conditions of oppression. Although Critical Librarianship, or #CritLib, is beginning to question some of the doctrinal assumptions underlying the practice of librarianship, an examination of some of the mechanisms with which white supremacy has been able to build an entire system of racial protectionism as an occupational sector that intersects with areas of significant public interest is an important and timely research concern.
Citation Key Alias: lens.org/069-727-951-165-240, pop00317
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Are urban public libraries websites accessible to Americans with Disabilities? - Liu, Yan Quan; Bielefield, Arlene; McKay, Peter (Universal Access in the Information Society, 2019)
This paper examines to what extent the 129 members of the Urban Public Libraries Council meet the Section 508 standards for accessibility under the Rehabilitation Act, the minimum acceptable standard for accessibility under the Americans with Disabilities Act. Using an HTML evaluation tool, WAVE, the HTML coding of the libraries’ homepages was evaluated according to the Section 508 criteria for accessibility. After one-to-one deep examination to determine the accessibility of the library websites, the results tended to mirror other studies showing that most library websites have some coding deficiencies that limit the accessibility of the websites. Notably, only 7 of the 122 libraries that were surveyed had no Section 508 errors present with their homepages.
7 citations (Crossref) [2023-10-31] tex.ids: ISI:000461373700014, lens.org/058-290-057-137-474, liuAreUrbanPublic2019 tex.address: [object Object] tex.affiliation: [object Object] tex.author-email: [object Object] tex.da: [object Object] tex.doc-delivery-number: [object Object] tex.eissn: [object Object] tex.journal-iso: [object Object] tex.keywords-plus: [object Object] tex.number-of-cited-references: [object Object] tex.publisher: [object Object] tex.research-areas: [object Object] tex.times-cited: [object Object] tex.type: [object Object] tex.unique-id: [object Object] tex.usage-count-last-180-days: [object Object] tex.usage-count-since-2013: [object Object] tex.web-of-science-categories: [object Object]
Keywords: ADA; Accessibility; Assistive technology; Compliance; Disability; HTML; Impairment; Libraries; Policy; Public libraries; Public library; Public policy; Section 508; Section508; Section 508; Universal usability; Urban libraries; Websites; dept.ils; peer-reviewed

An Analytical Study of Recommendation Systems in Chinese City Libraries / 城市图书馆馆藏资源推荐系统调查分析 - Guo, Q; Liu, Yan Quan; Wang, Y (Research on Library Science, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Differences, Complementarity and Convergence of University Library Mobile Service Platforms / 高校图书馆移动服务平台的差异、互补与融合 - Liu, Yan Quan; Zhao, F (Journal of the National Library of China, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

The Model and Challenges of Volunteer Service Mechanism in American Urban Libraries / 美国城市图书馆志愿者服务机制模式及面临的挑战 - Ren, X; Liu, Yan Quan (Library & Information, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Effect of different areal precipitation estimation methods on the accuracy of a reservoir runoff inflow forecast model - Zhong, Wei; Li, Ruirui; Liu, Yan Quan; Xu, Jin (IOP Conference Series: Earth and Environmental Science, 2018)
Areal precipitation estimation directly affects the accuracy of reservoir runoff inflow forecasts and flood dispatching decision-making. Because of the heterogeneous spatial and temporal precipitation distributions in large basins, inadequate precipitation stations normally have a negative impact on forecast accuracy. Using the Panjia-kou reservoir runoff inflow forecast as the research subject, this paper adopts the Thiessen polygon block, square grid computing, and DEM (digital elevation model) methods to estimate average regional areal precipitation. Based on the estimation, a model for the Panjia-kou reservoir runoff forecast is developed. The results indicate that different areal precipitation estimation methods have significantly different effects on the accuracy of the reservoir runoff inflow forecast. When the average regional precipitation estimation from the DEM method is used as an input to the model, the simulation results are accurate and are much better than those from the other two average regional precipitation estimation methods.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-272-786-643-178, pop00315
Keywords: Air pollution; Areal precipitation; Decision making; Different effects; Digital elevation model; Forecast accuracy; Forecasting; Grid computing; Precipitation distribution; Precipitation estimation; Research subjects; Reservoirs (water); Runoff; Runoff forecast; Surveying; dept.ils

The provision of mobile services in US urban libraries - Guo, Ya Jun; Liu, Yan Quan; Bielefield, Arlene (Information Technology and Libraries, 2018)
To determine the present situation regarding services provided to mobile users in US urban libraries, the authors surveyed 138 Urban Libraries Council members utilizing a combination of mobile visits, content analysis, and librarian interviews. The results show that nearly 95% of these libraries have at least one mobile website, mobile catalog, or mobile app. The libraries actively applied new approaches to meet each local community’s remote-access needs via new technologies, including app download links, mobile reference services, scan ISBN, location navigation, and mobile printing. Mobile services that libraries provide today are timely, convenient, and universally applicable.
3 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000435630900009, lens.org/084-687-778-320-226 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.ils; human; mobile application; peer-reviewed; printing; publication; review

Bullying in the library workplace - Kim, Hak Joon; Geary, Carol Anne; Bielefield, Arlene (Library Leadership & Management, 2018)
The primary purposes of the study were to investigate how often bullying occurs in libraries and whether bullying policies exist in libraries. The first survey questionnaire was sent to library personnel in the six New England states through statewide email distribution lists. Altogether 571 library staff members completed the survey. The second survey questionnaire was sent to large public and academic libraries in New England to see if they have anti-bullying policies in the workplace. The results of the study clearly showed there were significant reports of workplace bullying in all kinds of libraries. Nonetheless, not many libraries have policies that deal with this workplace challenge.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/185-409-335-946-838, pop00227 tex.type: [object Object]
Keywords: bullying; bullying polices; dept.ils; library policies; workplace bullying

Rural and small public libraries: challenges and opportunities - Real, Brian (Emerald Publishing, 2018)
Keywords: Rural libraries; Small libraries; dept.ils

The hidden history of the American Film Institute: the cold war, arts policy, and American film preservation - Real, Brian (The Moving Image: The Journal of the Association of Moving Image Archivists, 2018)
The American Film Institute (AFI) presently does relatively little in terms of film preservation, but its founding in 1967 led to the growth of many of the mechanisms that define the motion picture preservation community today. As this article reveals, the AFI's success in promoting ongoing federal government support for motion picture preservation cannot be separated from the political context of the Cold War. The AFI's first director, George Stevens Jr., had previously been the head of the Motion Picture Service of the United States Information Agency (USIA). This work with a public diplomacy agency was essential to his vision for the design and structure of the AFI. Likewise, the AFI was founded as an independent nonprofit, but with the promise of significant ongoing funding support from the National Endowment for the Arts (NEA). While this arrangement worked well at first, a change in presidential administrations and design flaws in the AFI's support mechanisms led to it being unable to meet the expectations of the very film preservation community it helped to foster.
0 citations (Crossref) [2023-10-31]
Keywords: dept.ils; peer-reviewed

Service mode of smart recommendation based on knowledge discovery - Wang, Y; Dong, X; Liu, Yan Quan (Research on Library Science, 2018)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Development path research on library smart service mode - Wang, Y; He, X; Liu, Yan Quan (Library Work and Study, 2018)
Keywords: dept.ils; ⛔ No DOI found

The present situation of mobile service in public libraries of China and the comparative analysis of public libraries in Eastern-Central-Western regions - Wang, Y; He, X; Liu, Yan Quan (Library, 2018)
Keywords: dept.ils; ⛔ No DOI found

An analytical review of sustainable development of American reading promotion policies - Dong, X; Liu, Yan Quan (Library, 2018)
Keywords: dept.ils; ⛔ No DOI found

Current situation and development trends of mobile services in the United States' urban libraries - Guo, Y; Liu, Yan Quan (Library and Information, 2018)
Keywords: dept.ils; ⛔ No DOI found

Forecasting of Chinese primary energy consumption in 2021 with GRU artificial neural network - Liu, Bingchun; Fu, Chuanchuan; Bielefield, Arlene; Liu, Yan Quan (Energies, 2017)
The forecasting of energy consumption in China is a key requirement for achieving national energy security and energy planning. In this study, multi-variable linear regression (MLR) and support vector regression (SVR) were utilized with a gated recurrent unit (GRU) artificial neural network of Chinese energy to establish a forecasting model. The derived model was validated through four economic variables; the gross domestic product (GDP), population, imports, and exports. The performance of various forecasting models was assessed via MAPE and RMSE, and three scenarios were configured based on different sources of variable data. In predicting Chinese energy consumption from 2015 to 2021, results from the established GRU model of the highest predictive accuracy showed that Chinese energy consumption would be likely to fluctuate from 2954.04 Mtoe to 5618.67 Mtoe in 2021.
55 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000414578400008 tex.article-number: [object Object] tex.unique-id: [object Object]
Keywords: China; Energy consumption; Energy planning; Energy security; Energy utilization; Forecasting; Forecasting modeling; Forecasting scenarios; Gated recurrent unit; Gross domestic products; Multi-variable linear regression; Multivariable systems; Neural networks; Primary energy consumption; Support vector regression (SVR); dept.ils; energy consumption; energy planning; forecasting scenarios; gated recurrent unit

Equitable access: Information seeking behavior, information needs, and necessary library accommodations for transgender patrons - Drake, Aubri A.; Bielefield, Arlene (Library & Information Science Research, 2017)
This study highlights the unique accommodations integral to welcoming transgender library patrons. Research shows transgender people have unique needs which differ from lesbian, gay, bisexual, and queer (LGBQ) individuals, and experience substantial barriers to obtaining quality library service. Most studies in the past exploring the needs of lesbian, gay, bisexual, and transgender library users focused exclusively on LGBQ users. This study surveyed adult transgender individuals (n = 102) with an online questionnaire. The majority of participants were white, designated female at birth, and under 40 years old. Survey respondents needed libraries to make accommodations for them to feel safe (p ¡ 0.001). The top 5 accommodations needed were recent transgender literature, gender identity or expression as part of library nondiscrimination policy, gender neutral, single-stall bathrooms where a key did not need to be requested, recent LGBQ literature), and an established remote process for name change.
15 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000408303500002, lens.org/107-673-593-066-888 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: dept.ils

Research on the current situation and countermeasures of the mobile information service in Chinese academic journals of library and information science - Zhao, F; Liu, Yan Quan; Wang, Y (Library and Information Service, 2017)
Keywords: dept.ils

The latest study of digital virtual reference service in Chinese top university libraries - He, X; Wang, Y; Liu, Yan Quan (Journal of Intelligence, 2017)
Keywords: dept.ils; ⛔ No DOI found

The latest study of reading promotion activities in American public libraries - He, X; Wang, Y; Liu, Yan Quan (Library and Information, 2017)
Keywords: dept.ils; ⛔ No DOI found

The election of Donald Trump to the presidency and the crisis of liberalism in librarianship - Sierpe, Eino (Journal of Radical Librarianship, 2017)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found